Report on the socioeconomic, humanitarian and human rights situation in the PalmaAfungi-Mocímboa area (Cabo Delgado) - Rufin, Jean-Christophe; Glowacki, Ingrid (Total Energies, 2023)
Patrick Pouyanné, Chairman and CEO of TotalEnergies, entrusted Jean-Christophe Rufin in December 2022, on behalf of the partners of the Mozambique LNG project, with an independent mission to assess the humanitarian situation in the province of Cabo Delgado where the project is located. Jean-Christophe Rufin, a recognized expert in the field humanitarian action and human rights, has carried out several investigation field trips in Mozambique. TotalEnergies publishes his report as well as the action plan decided by Mozambique LNG partners based on the recommendations of the report. The report recalls that the conflict in the province of Cabo Delgado has origins pre-dating the gas development projects and finds its roots in multiple factors not related to Mozambique LNG. It assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. The report assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. It notes an improved humanitarian situation in the north of Cabo Delgado, in particular with the return of the populations displaced by the conflict to the town of Palma and to a lesser degree to the town of Mocímboa da Praia. The report highlights the execution quality of the actions undertaken by Mozambique LNG and their positive impact on the living conditions of local population. However it recommends the establishment of a dedicated structure with increased resources to further expand these programs and to integrate them into an ambitious and sustainable strategy of local development covering the whole province, and not only guided by the security of the project site. Regarding the populations affected by the development of the Afungi industrial site, Jean-Christophe Rufin recommends several avenues of improvements to finalize in the best conditions the implementation of the resettlement plan and ensure the compensation of affected persons in accordance with the best practices. These improvements relate in particular to the update of the inventories of the affected persons’ assets, the payment timeline of compensations, the provision of agricultural land and the access to fishing areas.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; conflict / conflito; displaced communities / comunidades deslocadas; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; infrastructure - energy / infrastrutura - energia; natural resources - gas / recursos naturais - gás; private sector / setor privado; security / segurança; social action / ação social

Os espaços de participação e de exercício da cidadania, na voz de líderes associativos da província de Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
O texto descreve os obstáculos históricos ao desenvolvimento de organizações da sociedade civil (OSC) em Moçambique, que conheceram um cenário mais acolhedor na Constituição de 1990. Mecanismos de apoio à sociedade civil capacitaram líderes locais, tornando-os melhor conhecedores de dispositivos legais, capazes de reunir evidências e de exercer impacto junto das populações. Contudo, as organizações enfrentaram problemas internos, relacionados com a ausência de recursos financeiros, com a capacitação dos seus membros e com problemas de transparência e rotatividade. O sistema de ensino desenvolve poucas competências de cidadania activa e o Estado desconfia de iniciativas de consciencialização das populações em direitos fundamentais ou em mecanismos de participação cívica. A manutenção de uma cultura política de súbdito foi funcional à penetração do grande capital na exploração de recursos naturais. As OSC enfrentam obstáculos à participação, relacionados com a forte politização da sociedade, com a desconfiança governamental em relação ao escrutínio público, proibição de manifestações públicas e receio das suas lideranças, particularmente após o início do conflito armado. A proliferação de conflitos nas áreas da indústria extractiva e a inexistência de canais formais de participação e de acesso à justiça foram agudizaram tensões, habilmente capitalizadas por grupos violentos. A guerra dispersou os membros de OSC que timidamente floresciam nos vários distritos, retirando-lhes capacidade organizativa, de advocacia e pressão social. A chegada de organizações humanitárias internacionais em resposta à emergência pouco incluiu as associações locais, reproduzindo relações assistencialistas e de dependência. O texto demonstra a urgência de identificação de líderes locais, (re)capacitação das OSC e criação de fóruns de participação social, invertendo a crença de que a violência constitui a forma possível e legítima de participação.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - portuguese / português; authority / autoridade; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; governance / governação

Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Descolonizar os estudos urbanos em África. Conflitos armados e sustentabilidade urbana em Cabo Delgado. - Amaral, Silvia (Desafios para Moçambique 2022, 2022)
Este projecto de investigação pretende, assim, humildemente, contribuir para a descolonização dos estudos urbanos em Moçambique e Portugal, e para a transmutação dos traumas da guerra em oportunidades de desenvolvimento sustentável e prosperidade urbana.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; conflict / conflito; politics / política

Avaliação do Impacto da Subcomponente Subsídio para Crianças dos 0 aos 2. Componente de Subsídio para Criança do Programa Subsídio Social Básico na Província de Nampula em Moçambique Relatório da Pesquisa Final (24 meses) - Bonilla, Juan; Castro-Zarzur, Rosa; Seidenfeld, David; Peterman, Amber; Bruckauf, Zlata (American Institutes for Research e UNICEF, 2022)
Este relatório fornece os resultados finais da avaliação do Subsídio para Criança 0-2 de Moçambique. O Subsídio Criança 0-2 é um subcomponente do Programa de Subsídio Social Básico (PSSB), um programa nacional liderado pelo Ministério de Gênero, Criança e Ação Social (MGCAS). A avaliação coincide com a fase de arranque da intervenção, que aconteceu até 2021 em quatro distritos seleccionados da província de Nampula. A intervenção segue uma metodologia de 'dinheiro e cuidado' e inclui três componentes: (1) transferências de dinheiro, (2) um pacote de comunicação para a mudança social e de comportamentos (CMSC) com ênfase em nutrição (3) uma gestão de casos em temas de proteção social para os mais vulneráveis. A intervenção visa reduzir a pobreza e a vulnerabilidade social, fornecendo transferências em dinheiro para as cuidadoras principais de crianças pequenas com o objetivo geral de reduzir a pobreza, melhorar o bem-estar infantil e promover o acesso a serviços sociais básicos. Além disso, o componente de cuidados da intervenção pretende abordar a proteção complexa e inter-relacionada, bem como os riscos sociais, econômicos e de saúde, que as famílias-alvo enfrentam. A intervenção começou a ser implementada em setembro de 2018, e esta avaliação fornece evidências críticas sobre sua eficácia para informar a melhor forma de expansão da intervenção.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Ilha de Moçambique; GD - Lalaua; GD - Mogincual; GD - Nacala-a-Velha; GP - Nampula; L - portuguese / português; health - maternal and child / saúde - materno-infantil; social protection / proteção social

Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Agrarian Change in Northern Mozambique: A ‘New’ Dimension of Research in Light of the Conflict and Violence in Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Transformação Agrária No Norte De Moçambique: Uma “Nova” Dimensão De Pesquisa À Luz Do Conflito E Violência Em Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Stemming the Insurrection in Mozambique’s Cabo Delgado (International Crisis Group, 2021)
Principal Findings What’s new? Militant attacks and security force operations in Mozambique’s Cabo Delgado province have claimed nearly 3,000 lives, while displacing hundreds of thousands of people. Insecurity has prompted the suspension of a massive gas project. The Islamic State (ISIS) claims ties to the insurrection. Southern African governments are lobbying to send troops. Why did it happen? Mozambican militants have been motivated by grievances against a state that they see as delivering little for them, despite the development of major mineral and hydrocarbon deposits. Tanzanians and other foreigners have joined up, fuelling the insurrection. The country’s historically weak security forces have been unable to stem the onslaught. Why does it matter? Unaddressed, the insurrection could spread further, threatening national stability just as Mozambique is fulfilling a peace deal with the country’s main opposition group and heading into national elections in 2024. It could worsen instability along East Africa’s coast and present ISIS with a new front to exploit. What should be done? Maputo should accept targeted assistance for security operations to contain the insurrection, and avoid a heavy external deployment that could lead to a quagmire. Authorities should deploy aid to build trust with locals and open dialogue with militants. Regional governments should redouble law enforcement efforts to block transnational jihadist involvement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conter a Insurreição em Cabo Delgado, Moçambique - International Crisis Group (International Crisis Group, 2021)
O que há de novo? Os ataques de militantes e as operações das forças de segurança na província moçambicana de Cabo Delgado já custaram praticamente 3000 vidas e deslocaram centenas de milhares de pessoas. A insegurança levou à suspensão de um gigantesco projeto de gás. O Estado Islâmico (ISIS) reivindica laços com a insurreição. Os governos do Sul de Africa estão a exercer pressão para o envio de tropas. Porque aconteceu? Os militantes moçambicanos foram motivados pelo descontentamento em relação a um estado que, do seu ponto de vista, pouco fez por eles, apesar do desenvolvimento de depósitos minerais e de hidrocarbonetos significativos. Tanzanianos e outros estrangeiros juntaram-se, alimentando a insurreição. As forças de segurança, historicamente fracas, foram incapazes de conter a ofensiva. Porque importa? Se não for tratada, a insurreição pode vir a alastrar-se, ameaçando a estabilidade nacional enquanto Moçambique está a alcançar um acordo de paz com o principal grupo de oposição do país e antes das eleições nacionais de 2024. A instabilidade ao longo da costa de Africa Oriental poderia piorar e fornecer ao ISIS uma nova frente a explorar. O que deve ser feito? Maputo deveria aceitar uma assistência direcionada para suas operações de segurança, a fim de conter a insurreição, e evitar uma mobilização externa forte, que poderia levar a uma estagnação. As autoridades deveriam fornecer assistência para construir uma relação de confiança com os habitantes locais e um diálogo aberto com os militantes. Os governos regionais deveriam redobrar seus esforços em matéria de aplicação da lei para impedir a implicação jihadista transnacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; innovation / inovação

Situação humanitária em Cabo Delgado: milhares de deslocados continuam sem assistência e apoio do Governo e das agências internacionais - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Mais de 30.500 pessoas que abandonaram as suas casas devido aos ataques terroristas na vila de Palma em Março último continuam a enfrentar dificuldades de alimentação e de abrigo nos centros de acolhimento. A maioria está no centro de trânsito de Pemba e outros nos campos de deslocados de Metuge. A Matriz de Monitoria de Deslocamentos da Organização Internacional para as Migrações (OIM) continua a registar a chegada diária de deslocados que fogem da insegurança no norte de Cabo Delgado. As autoridades governamentais e as agências humanitárias interromperam, há mais de um mês, as operações de salvamento de pessoas que estão concentradas na vila de reassentamento de Quitunda, a menos de 30 quilómetros da vila de Palma. Devido à insegurança, as agências humanitárias não estão a prestar apoio a milhares de pessoas que estão em Quitunda, nas proximidades do acampamento de Afungi.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Observatory of Illicit Economies in Eastern and Southern Africa (Global Initiative Against Transnational and Organized Crime, 2021)
Illicit flows are a major part of the political and economic landscape of northern Mozambique. In South Africa, the trade in poached abalone and the trafficking of synthetic drug still remain joined today. The impact that heroin capsules have had in Durban in terms of violence, profitability and local demand for heroin. How illicit gold from South Sudan and the Democratic Republic of Congo flows through Uganda
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; conflict / conflito

Bispo de Pemba critica Nyusi: "Se eu fosse presidente, a minha presença seria outra. Estaria a falar de Cabo Delgado todos os dias" - Castro, Pedro Jorge (Moçambique para todos, 2021)
"Como é que um corrupto pode lutar contra si mesmo? É preciso uma espécie de revolução." As ameaças do governo. A guerra. E o deslocado que disparou contra insurgentes. Entrevista ao Bispo de Pemba.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - Pemba; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Total Suspends Mozambique LNG Temporarily on Security Threat - Francois De Beaupuy; Paul Burkhardt; Borges Nhamirre (Bloomberg.com, 2021)
French energy giant Total SE suspended its $20 billion liquefied natural gas project in Mozambique indefinitely due to an escalation of violence in the area, including a March attack by Islamic State-linked militants.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Financiamento da ADIN vai agravar a já insustentável dívida pública - Beula, Emídio (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Cenário Fiscal de Médio Prazo (CFMP 2022-2024), instrumento que marca o início do ciclo de planificação e orçamentação, avança cenários preocupantes em relação à evolução da dívida pública de Moçambique. Por exemplo, as projecções relativas às despesas públicas mostram que os encargos com a dívida pública, isto é, os pagamentos de juros relacionados com o serviço da dívida, passarão de 27.114,8 milhões de meticais em 2021 para 38.731,8 milhões de meticais em 2022, evidenciando um crescimento de cerca de 42,8%. Aliás, dados apresentados pelo CFMP indicam que a tendência deverá continuar crescente, pelo menos nos próximos três (3) anos, atingindo 44.734,2 milhões de meticais em 2024, o equivalente a uma subida de cerca de 65% em relação a 2021. Apesar dessas projecções, o Governo está a mobilizar um bilião de dólares para financiar as actividades da Agência de Desenvolvimento Integrado do Norte (ADIN) nas províncias de Cabo Delgado, Nampula e Niassa. O anúncio foi feito na semana passada pelo Ministro da Agricultura e Desenvolvimento Rural, Celso Correia, o governante responsável pela tutela administrativa da instituição. A mobilização do financiamento é feita antes mesmo da aprovação do plano estratégico da ADIN, denominado Estratégia Resiliente do Desenvolvimento Integrado do Norte. O documento ainda está em consulta pública nas três províncias onde serão implementados os projectos da agência de desenvolvimento da região norte.
Keywords: ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português

Cabo Ligado 45 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Following the rise of Islamist group al-Shabab in Cabo Delgado - Marie Toulemonde (The Africa Report.com, 2021)
A visual explanation of how Mozambique’s islamist group al-Shabab has grown over the years in the northern Cabo Delgado province.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; extractive industries / indústrias extractivas

An overview of foreign security involvement in Mozambique (defenceWeb, 2021)
A number of private security companies, foreign governments and militaries have become involved in Mozambique in its fight against the insurgency in Cabo Delgado, but the Mozambican government has so far largely limited external involvement. Nevertheless, there are a number of companies and countries providing security and security assistance to Mozambique. Private military contractors Russian […]
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Ligado 44 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Hundreds Missing After Mozambique Attack (Human Rights Watch, 2021)
Hundreds of people remain missing five days after an Islamic State (ISIS)-linked armed group known as Al-Shabab raided the town of Palma in Mozambique’s northern Cabo Delgado province, killing and wounding an unknown number of civilians and causing thousands to flee.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Cabo Ligado 43 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Cabo Ligado 42 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado 41 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Of zinc roofs and mango trees: tractors, the state and agrarian dualism in Mozambique - Cabral, Lídia (The Journal of Peasant Studies, 2021)
This paper reviews the latest mechanisation programme by the Mozambican government, asking how it is politically driven and how it shapes and is shaped by agrarian structures. Old ideas about agrarian dualism are reproduced today, albeit with a new language of public-private partnerships that are seen as potentially driving the modernisation of the peasantry. State-sponsored and privately-run service centres, featuring zinc roofed warehouses, are the government’s preferred route to modernisation, yet failing to reach the average farmer and understanding the motives and predicaments of private managers. Emerging small to medium farmers, who keep tractors under shady mango trees in their backyards, are also offering mechanisation services to their peers, which are instrumental to stepping up their production and commercial activities. The state’s push for mechanisation feeds uneven patterns of accumulation and social differentiation.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150.2020.1860026
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; agriculture / agricultura; government policy / politica governamental; private sector / setor privado

State Department Terrorist Designations of ISIS Affiliates and Leaders in the Democratic Republic of the Congo and Mozambique (United States Department of State, 2021)
The Department of State has designated the Islamic State of Iraq and Syria – Democratic Republic of the Congo (ISIS-DRC) and the Islamic State of Iraq and Syria – Mozambique (ISIS-Mozambique) as Foreign Terrorist Organizations under section 219 of the Immigration and Nationality Act, as amended. The Department has also designated ISIS-DRC and ISIS-Mozambique as […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

US hits IS groups in Mozambique, Congo with terror sanctions (AP NEWS, 2021)
WASHINGTON (AP) — The Biden administration on Wednesday designated two Islamic State affiliates in Mozambique and the Democratic Republic of Congo as “foreign terrorist organizations,” imposing...
Section: World News
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

A Insurgência Jihadi em Moçambique: Origens, Natureza e Início - Morier-Genoud, Eric (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Resultante de uma investigação com trabalho de campo em Cabo Delgado em 2018 e 2019, este novo Cadernos IESE nº 21, da autoria de Eric Morier-Genoud, explica a origem, natureza, e dinâmica da guerra no norte de Moçambique com base numa análise da historicidade e das dinâmicas internas das sociedades locais. Defende o argumento segundo o qual é mais produtivo pensar nos insurgentes do Al-Shabaab em termos da sua trajectória histórica, evoluindo de uma seita islâmista para um grupo armado jihadi violento, passando actualmente por um processo de internacionalização que poderá se evoluir de várias formas no futuro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Afinal, não é só Cabo Delgado! Dinâmicas da insurgência em Nampula e Niassa - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Nos últimos três anos e meio, Moçambique enfrenta uma violência armada desencadeada por um grupo de natureza jihadista. Com origens na zona norte de Cabo Delgado e localmente conhecido pela designação Al-Shabaab, o grupo surgiu como uma seita religiosa (Morier-Genoud, 2020) e, de seguida, constituiu-se numa unidade militarizada, tendo partido para a violência armada a 5 de Outubro de 2017. Baseado em trabalho de campo nas províncias de Cabo Delgado, Nampula e Niassa, este texto procura analisar a insurgência com base em dinâmicas de alguns distritos de Nampula e Niassa. Com enfoque nos factores do avanço da insurgência no terreno, o texto sublinha o argumento, segundo o qual, a compreensão do desenvolvimento da insurgência em Cabo Delgado passa, entre outros aspectos, pela análise das dinâmicas sociais, económicas e religiosas das províncias vizinhas, nomeadamente Nampula e Niassa, que se transformaram em espaços férteis de recrutamento, particularmente a partir de 2018. O argumento é desenvolvido em dois momentos. No primeiro momento, o texto procura identificar e analisar os principais factores que conduziram ao alastramento da insurgência para mais distritos de Cabo Delgado e à tentativa de instalação de células de tendência radical em alguns distritos de Nampula e Niassa. No segundo momento, focaliza-se a atenção para as dinâmicas de recrutamento a nível interno, com destaque para alguns distritos localizados na zona costeira de Nampula e na fronteira entre a província de Niassa e a Tanzânia.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Estabelecimento Da Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) Nas Províncias de Tete, Gaza, Nampula - RMDDH (CDD - Centro para Democracia e Desenvolvimento Mozambique, 2021)
A Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) está a levar a cabo actividades de identificação e mapeamento de defensores de direitos humanos nas províncias, que incluem pessoas singulares e organizações da sociedade civil que estão na linha de frente na luta pela defesa dos direitos humanos. Financiado pela OCISA, o trabalho iniciou em Abril último na Província de Tete, centro de Moçambique, onde a RMDDH realizou vários encontros com organizações da sociedade civil que trabalham na área dos direitos humanos e com instituições governamentais e estatais
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Gaza; GP - Nampula; GP - Tete; L - portuguese / português; civil society / sociedade civil

Mozambique: ExxonMobil again postpones final decision on Rovuma LNG (Mozambique, 2021)
US oil company Exxon has postponed for the third consecutive year the Final Investment Decision on the natural gas exploration project in Mozambique, putting the $30 billion investment in doubt. According to Bloomberg news agency, which quotes the company's Senior Vice President Neil Chapman, Nei
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

O que vi foi a morte: crimes de guerra no "cabo esqueçido" de Moçambique (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

What I saw is death: War crimes in Mozambique's forgotten cape (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Mozambique: Civilians killed as war crimes committed by armed group, government forces, and private military contractors – new report (2021)
The new report documents serious violations of international humanitarian law by all parties to the conflict in Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado Monthly: March 2021 - ACLED (ACLED, 2021)
In This Report: Analysis of the IS claim of the Palma attack in the context of the overall relationship between IS and the Cabo Delgado insurgency Discussion of growing tensions between displaced people, host communities, and aid organizations in districts with growing displaced populations Update on international involvement in the Cabo Delgado conflict and analysis of the role that South African companies Dyck Advisory Group and Paramount Group play in the conflict
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Waves and legacies: The making of an investment frontier in Niassa, Mozambique - García, Angela Kronenburg; Meyfroidt, Patrick; Abeygunawardane, Dilini; Sitoe, Almeida (AfricArXiv, 2021)
To understand how land-use frontiers emerge, we studied the actors driving investments in Niassa province, Mozambique. Our ethnographic research over 2017-2018 among commercial agriculture and forestry investors shows that successive waves of actors with different backgrounds, motives and business practices, arrived in Niassa to establish farms or plantations yet repeatedly failed. Waves come and go but leave sediments – legacies – that add up to gradually build the conditions for a frontier to emerge. The accumulation of these legacies has given rise to a new wave by actors from within the region, indicating that over time endogenous processes may replace externally-driven waves.
type: article
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; Northern PEA; agriculture / agricultura; private sector / setor privado

Ten Conflicts to Worry About in 2021 (ACLED, 2021)
A review of key developments in 2020 with a look toward trends to watch in the coming year.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Mozambique: How Total plans to protects its $15bn major gas project - Le Bec, Christophe (The Africa Report.com, 2021)
Total is going ahead with its Mozambique LNG project despite a major armed insurgency in Cabo Delgado. This article discusses plans to secure its Afungi facility, including security forces involved. Facility employment is projected to triple by 2022, from 5,000 in 2020 to 15,000 by 2022.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; employment / emprego; extractive industries / indústrias extractivas; private sector / setor privado

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

An Overview of the Policy and Market Landscape of Tobacco Production and Control in Mozambique - Nguenha, Nicole; Cunguara, Benedito; Bialous, Stella; Drope, Jeffrey; Lencucha, Raphael (International Journal of Environmental Research and Public Health, 2021)
Background: Tobacco growing has been considered a mainstay of Mozambique’s economy, but there is a dearth of analysis of the tobacco policy landscape in the country. Methods: Review of government and non-government documents and academic papers addressing Mozambique’s tobacco-growing history, the changes in the political economy of tobacco, and health policies addressing tobacco use and prevention of noncommunicable diseases. Results: Despite its tobacco growing and exporting history, the contribution of tobacco to the economy has been in steady decline in the past two decades, including in the areas dedicated to growing. At the same time there has been an increase in multinational control of the tobacco economy. In parallel, Mozambique’s commitment to addressing the growing burden of noncommunicable disease and accession to the Framework Convention on Tobacco Control indicate a potential for internal government tensions to balance immediate economic interests with long term health goals. Conclusions: With the decline in tobacco share of the overall economy, Mozambique may be well-positioned to explore alternative, sustainable livelihoods for farmers that grow tobacco, but it must overcome inter-sectoral barriers and advocate for a whole of government approach to address the health and economic impact of tobacco.
Number: 1 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Publisher: African Development Bank Group 978-9973-9854-5-3 (electronic)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

Formalizing artisanal and small-scale mining in Mozambique: Concerns, priorities and challenges - Hilson, Gavin; Mondlane, Salvador; Hilson, Abigail; Arnall, Alex; Laing, Tim (Resources Policy, 2021)
This paper reflects critically on efforts made to formalize artisanal and small-scale mining (ASM) – low-tech, labour-intensive mineral extraction and processing – in Mozambique. Drawing on findings from interviews with policymakers, representatives from ASM associations and 200 individual miners, the paper captures the details of the country’s ASM formalization experience. Findings reveal that despite showing considerable promise at first, the drive to formalize ASM in Mozambique, which spans three decades, has lost considerable momentum. A bureaucratic licensing scheme, overlapping responsibilities at the Estatuto Orgaˆnico do Minist´erio dos Recursos Minerais e Energia (MIREME), and a shortage of information about miners have contributed to this slowdown. The themes underpinning the efforts to formalize ASM in Mozambique are not new but the case itself has its own unique nuances and storylines.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Inquérito Agrário Integrado 2020 - MADER (República de Moçambique - Ministério da Agricultura e Desenvolvimento Rural Direcção de Planificação e Políticas (DPP), 2021)
O crescimento agrícola em Moçambique é uma fonte essencial para promover o crescimento económico do País em geral e das famílias rurais em particular. O Programa do Governo para o Sector Agrário, em harmonia com a política económica do País, orienta-se para o alcance de grandes objectivos estratégicos, nomeadamente: (1) Segurança Alimentar; (2) Aumento do Rendimento Familiar; (3) Criação de Emprego/Inclusão Social e (4) Aumento da Produção e Produtividade. Este documento ilustra, de forma simples e clara, a situação e a dinâmica da agricultura em Moçambique durante o ano de 2020. O Inquérito Agrário Integrado (IAI 2020), indica que existem no país cerca de 4.3 milhões de explorações agro-pecuárias, das quais 4.167.702 (97.8%) são pequenas, 93.183 (2%) são médias, e 873 (<1%) são grandes explorações. Do total de cerca de 4.3 milhões de explorações (Pequenas e Médias), cerca de 6.9% receberam informação ou conselho técnico de extensão, 39.9% tiveram acesso à informação sobre preços e 0.6% acesso à crédito. A área cultivada foi de cerca de 5.5 milhões de hectares, onde 5.5% das explorações utilizaram pesticidas nos seus campos, 8.8% usaram estrume, 7.8% utilizaram fertilizantes químicos e 9.1% usou a rega. As principais culturas em diversas explorações são o Milho, Arroz, Mapira, Amendoim Pequeno, Feijão Nhemba, Feijão Boer, Mandioca, Algodão e Canade-açúcar. Grande parte das explorações cultivam Milho (83.8%), 23.6% Amendoim Pequeno, 18.3% Mapira, 12 .8% Arroz e 3.8% Mexoeira. O IAI 2020, realizado pela primeira vez com referencial distrital, é um Marco Estatístico e principal fonte de dados do sector agro-pecuário, assim como marco amostral, pois fornece dados fiáveis desagregados até ao nível Distrital, para apoiar o processo de planificação e tomada de decisão a todos níveis, baseadas em evidências científicas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura; demographics / demografia

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Jovens moçambicanos descontentes com falta de oportunidades (DW.COM, 2020)
No Dia Mundial da Juventude, jovens da província moçambicana de Nampula queixam-se da falta de emprego, de habitação e de acesso ao crédito financeiro. O novo coronavírus também é um dos maiores problemas atualmente.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; employment / emprego; youth / juventude

Humanitarian Response Plan Mozambique (United Nations Office for the Coordination of Humanitarian Affairs (OCHA), 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

Mozambique: Analytical Report on Decentralisation - Salimo, Padil (Asociação Nacional de Municipios de Mozambique - ANAMM, EU and UCLG Africa, 2020)
The United Cities and Local Governments of Africa (UCLGA) commissioned this report in coordination with the National Association of Municipalities of Mozambique (ANAMM) to analyse the political economy of decentralisation of Mozambique. The report provides information in support of the ANAMM discussion and dialogue toward the new European Union (EU) programming process of cooperation with local authorities (LAs) for the 2021-2027 period. This report was developed in line with another called “Compendium of References” which is also part of the preparation for the EU programming process of cooperation with the Las. The analytical report on political economy pretends to explore the extent to which the central government embraced the conceptualisation of territorial development, the level of commitment of central government in recognizing the role of local authorities in the territorialisation of the national development agenda, and the opportunities and constraints created by the decentralisation system for the empowerment of local authorities as developmental actors. The political economy analysis catches the key aspects of how political and economic power influences the way how decentralisation is implemented and contested, the incentives behind the political actors and interests groups and how they impact the decentralisation reforms outcomes. The report serves as a background document to a seminar of the members of the ANAMM, which is part of a process of building consensus over the key priority action to include in the municipalities’, or interchangeably called in the report also as local authorities, roadmap for dialogue with the central government and the EU Delegation in Maputo, Mozambique. The expected result involves the following: (i) An analysis of the political economy of decentralisation, the feasibility of the new local authorities (LAs) driven political agenda and the opportunities and constraints created by the decentralisation reforms; (ii) An overview of the state of art regarding the territorialising of national policies and global agendas including SDGs, in terms of both policies and programs adopted in the framework of the national development plan; (iii) A SWOT quick analysis of the ANAMM; and (iv) The state of the art concerning the territorialisation of national policies and global programs, including Sustainable Development Goals (SDGs), both at the level of policies and programs implemented within the framework of the National Development Plan.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The politics of domestic gas: The Sasol natural gas deals in Mozambique - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime (The Extractive Industries and Society, 2020)
This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from ‘domestic natural gas’. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

The Secret to the Northern Mozambique Insurgency’s Success - Emilia Columbo (War on the Rocks, 2020)
This has been a banner year for Ahlu-Sunnah Wa-Jama (ASWJ) — or al-Shabaab, as locals call it — operating in northern Mozambique. Between January and
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

First confirmed occurrence of the yellow fever virus and dengue virus vector Aedes (Stegomyia) luteocephalus (Newstead, 1907) in Mozambique - Abílio, Ana Paula; Kampango, Ayubo; Armando, Eliseu J.; Gudo, Eduardo S.; das Neves, Luís C. B.; Parreira, Ricardo; Sidat, Mohsin; Fafetine, José M.; de Almeida, António Paulo G. (Parasites & Vectors, 2020)
Mozambique, same as many other tropical countries, is at high risk of arthropod-borne virus (arbovirus) diseases and recently two dengue virus (DENV) outbreaks occurred in the northern part of the country. The occurrence of some important vector species, such as Aedes (Stegomyia) aegypti (Linnaeus) and Ae. (Stg.) albopictus (Skuse), besides several other sylvatic vectors, have been reported in the country, which may indicate that the transmission of some arboviruses of public health importance may involve multiple-vector systems. Therefore, knowing the occurrence and distribution of existing and the new important vectors species, is crucial for devising systematic transmission surveillance and vector control approaches. The aim of this study was to map the occurrence and distribution of mosquito species with potential for transmitting arboviruses of human and veterinary relevance in Niassa Province, Northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lago; GP - Niassa; L - english / inglês; health / saúde

Indonesia's Guaranteed Microfinance Programme (KUR): Lessons from the First Stage of Implementation - ProQuest (2020)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Influence of institutional factors on the performance of the agricultural sector in Mozambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Abstract: This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; institutions / instituições

Influência de Factores Institucionais no Desempenho do Sector Agrário em Moçambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Este artigo constitui uma revisão das instituições e do desempenho do sector agrário em Moçambique, aplicando um quadro de análise adaptado à avaliação da ligação entre as instituições e o desenvolvimento económico. Na primeira parte, apresenta-se informação sobre o desempenho do sector entre 2008 e 2017, verificando-se redução da produtividade e da produção per capita de alimentos. A segunda parte oferece uma análise sobre a medida em que, e o modo como, a evolução das instituições do sector influenciou o desempenho da Agricultura nesse período. Verifica-se ter havido instabilidade institucional que afectou o desempenho do sector, não se tendo logrado travar a redução da produção e da produtividade, o que eventualmente reflecte um ambiente socioeconómico e institucional mais amplo, isto é, além do sector agrário. Na terceira parte, colocam-se alguns elementos de reflexão sobre questões institucionais que possam contribuir para o debate sobre o desenvolvimento futuro do sector agrário. Sugere-se a necessidade de pensar o futuro da Agricultura em Moçambique numa perspectiva de longo prazo, com foco na adopção e estabilização de um quadro institucional orientado para o aumento da produtividade agrária e para a preservação do ambiente.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura; institutions / instituições

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique LNG Project Could Be Transformational For Mozambique — If Western Environmentalists Don’t Interfere | Africa Oil & Power (2020)
NJ Ayuk discusses the Mozambique LNG project.
Section: Interviews
Keywords: #Reporting & Media / Reportagem & Mídia; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; private sector / setor privado

Mediating bureaucrats: embedded economic action in the Mozambican sugar industry - Buur, Lars; Nystrand, Malin J. (The Journal of Modern African Studies, 2020)
This article develops the concept of ‘mediating bureaucrats’ by exploring their role during liberal reforms that led to rehabilitation of the sugar industry in Mozambique. By focusing on how relations between the state, government and business are mediated by a group of cadres who have occupied positions in different social domains, the article argues that these ‘mediating bureaucrats’ cannot easily be identified in one-dimensional terms as belonging to either the public or private sector, the state or the market. It is argued that as ‘socially embedded actors’, the group of ‘mediating bureaucrats’ are in a position to translate and mediate between diverse and sometimes conflicting interests and aspirations of the state, the government and business. We use the rehabilitation of the sugar industry in Mozambique to show how mediating bureaucrats adopted two practices – muddling through and translation – in order to straddle conflicting interests during different reform initiatives in post-independence Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Insurgência: No lançamento da ADIN Nyusi ameaça reagir em caso de atentado a coesão - Anacleto, Delfim (Deutsche Welle (DW), 2020)
O norte de Moçambique passa a partir de hoje a contar com uma Agência de Desenvolvimento integrado para promover o crescimento económico e social. E em Pemba, Filipe Nyusi falou com o bispo de Pemba sobre a insurgência.
Keywords: *indexed; ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Total signs agreement with the Government of Mozambique regarding the security of Mozambique LNG project (Total.com, 2020)
Map Mozambique
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; private sector / setor privado

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Depois da ADIN, Celso Correia “ganha” Agência do Zambeze e passa a controlar o desenvolvimento do centro e norte de Moçambique - Nuvunga, Adriano (Centro para a Democracia e Desenvolvimento (CDD), 2020)
Tal como procedeu no caso da passagem da tutela da ADIN para Celso Correia, o CDD defende que a Agência do Zambeze deve estar sob tutela do Conselho de Ministros e a sua direcção deve prestar contras ao Primeiro-Ministro. À semelhança da ADIN, a Agência do Zambeze tem uma visão holística de desenvolvimento e uma actuação transversal que abrange todos os sectores económicos e sociais do Governo, pelo que não faz sentido a sua direcção responder a um Ministro responsável por um único sector, seja ele de Economia ou de Desenvolvimento. Pela sua importância estratégica para o desenvolvimento do pontecial do Vale do Zambeze, a Agência do Zambeze deve ser dirigida por gestores de reconhecido mérito recrutados através por um concurso público transparente e independente, como forma de evitar a gestão danosa e as infracções financeiras denunciadas pelo Tribunal Administrativo em 2018. Quando o Governo de Armando Guebuza criou a Agência do Zambeze em 2010, o objectivo principal era de “assegurar a eficácia e a eficiência no desenvolvimento da parte nacional da bacia hidrográfica do Vale do Rio Zambeze, uma das regiões cujo potencial de recursos e as possibilidades de aproveitamento estudadas apontam como susceptível de, rapidamente, contribuir para o desenvolvimento e crescimento económico e humano auto-sustentado do país”. Volvidos 10 anos depois, a Agência do Zambeze ainda não deu sinais de estar a explorar as potencialidades do Vale do Zambeze para dinamizar o desenvolvimento das províncias do centro do país, que concentram boa parte da população pobre de Moçambique. O Vale do Zambeze tem potencial energético, grandes depósitos de minerais como carvão e ferro, para não falar do potencial agro-pecuário subaproveitado. Não foi por acaso que o político português Almeida Santos uma vez declarou: “Quem tem o Vale do Zambeze não pode ser um país pobre”6. Mas os cerca de 12 milhões de pessoas que vivem nas quatro províncias atravessadas pelo Vale do Zambeze continuam num vale de pobreza.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; rural development / desenvolvimento rural

Broadening the Analysis of Peace in Mozambique: Exploring Emerging Violence in Times of Transnational Extractivism in Cabo Delgado - Alberdi, Jokin; Barroso, Manuel (Global Society, 2020)
This article explores the contemporary expressions of violence and oppression linked to the action of the extractive industry in the northern province of Cabo Delgado, Mozambique. Twenty-five years after the signing of the General Peace Agreement, the debate on peace in the country has remained confined to the resurgence of armed clashes between RENAMO combatants and State security forces in recent years. It is proposed here, however, that the current range of violence that challenge peace in Mozambique is broader and more diverse, requiring an analysis that considers the arrival of transnational extractivism. This study, taking Cabo Delgado province as a case-study, aims to broaden the scope of academic debates by establishing a dialogue with the practice of local peacebuilding, and contributions from the critical political economy of development and the collective capability approach.
Publisher: Routledge _eprint: https://doi.org/10.1080/13600826.2020.1772730
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; extractive industries / indústrias extractivas

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Face ao conflito no norte, o que Moçambique pode aprender da sua própria guerra civil (1976 – 1992)?: Uma análise das dinâmicas da insurgência em Cabo Delgado - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Analisa as dinâmicas da insurgência em Cabo Delgado e procura interrogar o que Moçambique pode aprender dos seus ciclos de violência armada, particularmente a guerra civil, para fazer face ao actual conflito no Norte do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

How Do Donor-led Empowerment and Accountability Activities Take Scale into Account? Evidence from DFID Programmes in Contexts of Fragility, Conflict and Violence - Anderson, Colin; Fox, Jonathan; Gaventa, John (2020)
Development donors invest significantly in governance reform, including in contexts characterised by conflict and fragility. However, there is relatively little comparative study of their change strategies, and little understanding of what works and why. This paper explores the strategies of six recent DFID-funded programmes in Mozambique, Myanmar, and Pakistan with empowerment and accountability aims. Document review and field interviews are used to analyse the application of multi-scalar or multi-level change strategies, since such approaches are hypothesised to potentially generate more leverage for public accountability reforms. Analysis suggests that these strategies can strengthen citizen ability to navigate governance systems to resolve problems and claim accountability, and can bolster pro-accountability coalitions’ internal solidarity and external legitimacy. Multi-level strategies also appear associated with establishing more significant pressure for reform than exclusively local or national approaches. Yet conventional project reporting focuses on counting activities and outputs rather than analysing the dynamic, interactive processes at work in these strategies, and few evaluations are publicly accessible. To fully understand what kinds of action strengthen citizen demands for accountability requires a more transparent and rigorous approach to learning from donor-led governance interventions.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

Desenvolvimento socioeconómico de Cabo Delgado num contexto de conflito - João Feijó; António Souto; Jerry Maquenzi (Observador Rural, 2020)
Um conjunto de contradições internas e de longa duração estruturam as relações socioeconómicas na província, estando em grande medida na origem da conflitualidade actual. Não obstante a crescente interferência de factores externos na dinamização do conflito, os dados disponíveis permitem-nos concluir que, enquanto persistirem elementos internos de contradição, não será possível encontrar uma solução sustentável para o conflito. Não obstante o conflito implicar, inevitavelmente, uma intervenção militar, para prover a segurança das populações e de bens, as profundas contradições internas existentes obrigam à realização de um plano de desenvolvimento social e económico, entendido como a melhor estratégia de contra-insurgência, limitando o alastramento do conflito armado por outras zonas da província marcadas pela pobreza e por históricas relações de protesto em relação ao Estado. Uma vez que as informações são escassas e imprecisas e a situação militar no terreno é bastante imprevisível, torna-se difícil definir linhas gerais para um plano de intervenção. Não obstante, neste documento pretende-se apresentar um conjunto de elementos que devem ser considerados, de forma coerente, na implementação de qualquer projecto de desenvolvimento, distinguindo as diferentes áreas socioeconómicas de intervenção na província de Cabo Delgado, em função da realidade actual.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict / conflito; economic development / desenvolvimento económico

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Centro de Integridade Pública (Public Integrity Centre), 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Protecção social em contexto de terrorismo: que implicações tem a insurgência islâmica nos mecanismos formais de protecção social em Moçambique? - Siúta, Moisés (2020)
O impacto do terrorismo em Moçambique é uma realidade que não se restringe apenas à zona Norte do país. O IDeIAS nº 137, da autoria de Moisés Siúta, procura discutir as suas implicações nos sistemas formais de protecção social tendo em conta o desafio que enfrentam de garantir protecção e bem-estar social da população nas regiões mais afectadas sem, no entanto, deixar para trás a população vulnerável a diversos riscos como seca, cheias e a pandemia.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito; social protection / proteção social; ⛔ No DOI found

Spatio-temporal patterns of wildfires in the Niassa Reserve –Mozambique, using remote sensing data - Nhongo, Eufrásio; Fontana, Denise; Guasselli, Laurindo (2020)
Wildfires are among the biggest factors of ecosystem change. Knowledge of fire regime (fire frequency, severity, intensity, seasonality, and distribution pattern) is an important factor in wildfire management. This paper aims to analyze the spatiotemporal patterns of fires and burned areas in the Niassa Reserve between 2002-2015 using MODIS data, active fire product (MCD14ML) and burned area product (MCD64A1). For this, the annual and monthly frequencies, the trend of fires and the frequency by types of forest cover were statistically analyzed. For the analysis of the spatial dynamics of forest fires we used the Kernel density (Fixed Method). The results show a total of 20.449 forest fires and 171.067 km2 of burned areas in the period 2002-2015. Fire incidents were highest in 2015, while the largest burned areas were recorded in 2007. The relationship between increased fires and burned areas is not linear. There was a tendency for fires to increase, while for burnt areas there was stabilization. Forest fires start in May and end in December. August-October are the most frequent period, peaking in September. Fires occur predominantly in deciduous forests and mountain forests because of the type of vegetation and the amount of dry biomass. There is a monthly spatial dynamics of wildfires from east to west in the reserve. This behavior is dependent on vegetation cover type, fuel availability, and senescence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; natural disasters / desastres naturais

The implementation of ASEAN single window in Indonesia as an effort to facilitate the flow of import and export in Indonesia - Arifin, Jamilah (2020)
On 9 December 2005, All ASEAN member countries signed the Agreement to Establish and Implement the ASEAN Single Window. ASEAN Single Window (ASW) is a one window system that connects ASEAN countries or National Single Window (NSW) to facilitate the electronic exchange of customs data that can be used by traders to obtain permits, customs clearance, and other documents. Indonesia has been implementing this Agreement from 2008 with the system of Indonesia National Single Window (INSW) in order to improve the smooth flow of goods and the performance of export-import services. By using the normative legal research, the research aims to determine the implementation of the ASEAN Single Window (ASW) system as an effort to facilitate the flow of exports and imports in Indonesia. The research shows that the implementation of ASEAN Single Window in Indonesia through Indonesia National Single Window System has helped improve efficiency and import export activities through its service contribution.
Keywords: *indexed; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Economic brief - The Africa Infrastructure Development Index (AIDI) 2020 - African Development Bank (African Development Bank, 2020)
The development of infrastructure in Africa is critical for fostering economic growth and improving the living standards of Africans. It contributes significantly to human development, poverty reduction, and the attainment of the Sustainable Development Goals (SDGs). Investment in infrastructure accounts for over half of the improvements in economic growth in Africa witnessed over the last decade and has the potential to contribute much more, given a conducive environment.
Publisher: African Development Bank Group
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Geografia Eleitoral e Insurgência em Cabo Delgado - Brito, Luís de (Desafios para Moçambique, 2020)
This chapter looks at the origins of the extremist insurgency in Cabo Delgado and posists that to understand its origins, we must look beyond religious extremeism and to other factors in order to analyse the situation from difference perspectives. This study looked at electoral data in Cabo Delgado to determine if there is a relationship bwtween voting patterns, including abstention, and political cleavages and social conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; electoral geography / geografia eleitoral

BTI 2020 Mozambique Country Report - BTI (2020)
“Mozambique faces five major challenges: violence between political camps, impunity with regard to corruption, violations of human rights, the debt crisis and the security threat of Islamist terrorism.”
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

Ugandenses e Tanzanianos do Al-Shabaab: um olhar à dimensão internacional do conflito em Cabo Delgado - Chichava, Sergio (Desafios para Moçambique, 2020)
O conflito militar que, desde 5 de Outubro de 2017, se abate sobre Moçambique, com particular incidência na província de Cabo Delgado e protagonizado por um grupo localmente conhecido por Al-Shabaab, cuja pretensão é substituir o Estado laico por um Estado regido pela Sharia, tem sido regularmente descrito pelas autoridades moçambicanas como tendo, além de uma dimensão interna, uma componente externa. Desde o início do conflito, as autoridades locais falam da prisão ou da procura de vários estrangeiros que estariam a treinar, financiar e dirigir a «insurgência» em Cabo Delgado com vista a retardar o desenvolvimento do País e a explorar ilegalmente diversos recursos naturais. De entre os diversos estrangeiros frequentemente mencionados, o destaque vai para tanzanianos e ugandenses. Por seu turno, o Al-Shabaab tem vindo a reclamar uma dimensão internacional, declarando fidelidade ao Estado Islâmico (EI) ou Daesh. Ao que tudo indica, o Daesh também reconhece o Al-Shabaab, que designa por «soldados do Califado» pertencentes ao Estado Islâmico da Província da África Central (ISCAP, no acrónimo inglês), uma região cujos contornos geográficos ainda não estão bem claros, mas que englobaria actualmente, além Moçambique, a República Democrática do Congo (RDC), País onde está baseado o grupo islamista ugandês Forças Democráticas Aliadas (ADF), que também tem sido apresentado nalguns fóruns como tendo relações com o Al Shabaab em Moçambique, através da presença de alguns dos seus militantes neste País, ou através do recrutamento e treino de jovens moçambicanos na RDC. Com base nos elementos acima, o objectivo deste texto é fazer uma breve análise da componente internacional do AlShabaab, olhando para a sua ligação com a Tanzânia, o Uganda e o EI. Mais precisamente, olhando para o perfil dos cidadãos ugandeses e tanzanianos que têm sido referenciados como sendo do Al-Shabaab, o texto procura responder às seguintes questões: quem são os tanzanianos e ugandeses do Al-Shabaab? Como chegaram a Moçambique? O que pretendem? Porque escolheram a província de Cabo Delgado? Será o Al-Shabaab uma filial do Estado Islâmico? Para responder a estas questões, primeiro apresenta-se o perfil dos tanzanianos e ugandeses do Al-Shabaab; a seguir, apresentam-se algumas hipóteses sobre as suas pretensões; e, por último, abordam-se alguns elementos sobre a possível ligação do Al-Shabaab ao Daesh ou ao EI.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
978-84-09-17639-7
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, João (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
ISBN: 9782490093182 OCLC: 1199064112
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Introdução - Forquilha, Salvador (Desafios para Moçambique 2020, 2020)
Trinta anos depois da aprovação da primeira Constituição multipartidária da história do País,2 Moçambique continua a enfrentar grandes desafios no processo da construção democrática. Com efeito, não só as instituições que resultaram das reformas políticas no âmbito da nova Constituição têm demonstrado fragilidades no seu funcionamento, como também as regras do jogo político têm sido marcadas por uma certa instabilidade, consubstanciada, por exemplo, nas sucessivas revisões da legislação eleitoral. Nos últimos índices de democracia,3 Moçambique tem registado recuos significativos na sua pontuação. Depois de ter passado de regime híbrido para regime autoritário (The Economist, 2019), o País passou da posição 116, em 2018, para a posição 120, em 2019 (The Economist, 2020). No que se refere à situação económica, a trajectoria do País tem sido marcada por crises e contradições, resultantes, essencialmente, das estruturas sociais de produção, das dinâmicas de dependência e do sistema social de acumulação (Castel-Branco, C.N., 2020a). No plano social, apesar de ter havido uma ligeira melhoria em termos de bem-estar e uma redução percentual da taxa de pobreza de consumo em 5 % entre 2008/2009 e 2014/2015, de acordo com os dados do Inquérito aos Orçamentos Familiares (IOF) 2014/2015, análises indicam que ainda persistem diferenças significativas regionais e entre os espaços urbano e rural ao longo do País. Com efeito, «a redução da pobreza no período entre 1996/1997 e 2014/2015 foi substancial tanto nas áreas rurais como urbanas, mas a redução foi mais acentuada nas áreas urbanas entre 2008/2009 e 2014/2015. A nível regional, evidencia-se que o Norte piorou a própria situação em termos de taxa de pobreza de consumo, passando de 45 % para 55 %, enquanto o decréscimo das taxas de pobreza no Centro e no Sul foi, respectivamente, de 10 e 18 pontos percentuais. Entre 2008/2009 e 2014/2015, a pobreza diminuiu em todas as províncias do Centro e Sul, particularmente em Maputo (província e cidade), enquanto nas três províncias do Norte as taxas de pobreza estagnaram ou cresceram» (Arndt et al., 2018: 311). Os dados acima também indicam que a pobreza é muito resiliente em relação ao crescimento económico – no mesmo período em que baixou 5 % (a uma média anual de -0,8 %) o PIB cresceu 50 % (a uma média anual de 7 %), revelando que o padrão de crescimento económico é pouco eficiente a reduzir pobreza.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; poverty / pobreza

Face ao conflito no norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgago - Forquilha, Salvador; Pereira, João (Desafios para Moçambique 2020, 2020)
A história de Moçambique dos últimos 50 anos tem sido marcada por ciclos de violência armada de contestação ao Estado, não só colonial, como também pós-colonial. Com efeito, desde a guerra anticolonial levada a cabo pela Frente de Libertação de Moçambique (Frelimo), passando pela guerra civil, que opôs a Resistência Nacional Moçambicana (Renamo) ao Governo da Frelimo, até às crises político-militares pós-eleitorais, a violência armada tem estado presente no processo da construção do Estado em Moçambique. No início de Outubro de 2017, começou uma outra contestação violenta ao Estado na província de Cabo Delgado. No dia 5 de Outubro de 2017, um grupo de homens armados atacou as instituições do Estado na vila sede de Mocímboa da Praia. Inicialmente associado a um banditismo de mera perturbação da ordem pública, o fenómeno ganhou rapidamente proporções alarmantes. Os ataques começaram a multiplicar-se. Dois meses depois do primeiro ataque, a Polícia já havia detido 251 suspeitos, dos quais 37 eram cidadãos de nacionalidade tanzaniana (O País, 2017). Em Dezembro de 2017, a Polícia da República de Moçambique, ao mais alto nível, esteve na zona e visitou os distritos de Mocímboa da Praia e Palma. No comício popular que realizou na vila sede de Mocímboa da Praia, o Comandante Geral da Polícia, Bernardino Rafael, deu um «ultimato» aos atacantes de Mocímboa da Praia, decretando sete dias para se entregarem às autoridades (O País, 2017). No entanto, a violência continuou e, nas semanas e meses que se seguiram ao ataque à vila sede de Mocímboa da Praia, a situação de segurança piorou no terreno e os ataques espalharam-se para outros distritos da zona norte de Cabo Delgado. Entre finais de Março e meados de Abril de 2020, a violência armada atingiu níveis nunca vistos antes, com o assalto e a ocupação temporária de quatro vilas nos distritos de Mocímboa da Praia, Quissanga, Muidumbe e Ibo. Que factores estão na origem do avanço da insurgência no terreno? Que tipo de relação se vai desenvolvendo entre os insurgentes e as populações locais? Existe algum potencial para que a insurgência se alastre para o Sul, em direcção à zona costeira de Nampula? Como tem vindo o Estado a responder à insurgência? Estas perguntas são uma parte importante do programa de pesquisa intitulado «Estado, violência e desafios de desenvolvimento no Norte de Moçambique», em curso no IESE desde Agosto de 2019.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Decentralization reforms in Mozambique: The role of institutions in the definition of results - Forquilha, Salvador; UNU-WIDER (UNU-WIDER, 2020)
Abstract: With the introduction of the economic reforms in the late 1980s, the opening up of the political arena and the end of the civil war in the early 1990s, the decentralization process began in Mozambique. Different research developed in recent years shows that, as is the case in other countries in sub-Saharan Africa, the impact of the decentralization reforms on the promotion of local development and the strengthening of democracy in Mozambique is modest. How can this modest impact be explained? Based on three important reforms in the decentralization process in Mozambique, namely the ‘7 million’, municipalization and decentralized provincial governance, this article seeks to answer this question by analysing how different aspects of the institutions affect the results of the reforms. The main argument in the article underlines the idea according to which the results of the decentralization reforms in Mozambique are constrained by the nature and by the operation mechanisms of the political system. Of these institutional factors/constraints, state capacity and independence from private interests, particularly political groups, stand out in the three reforms analysed throughout this article. In this context, the reforms develop according to group interests, particularly party political interests, which capture the state and use the reforms as a mechanism for maintaining and bolstering political power. In this sense, rather than being a means of improving the provision of public services and strengthening democracy, decentralization works more as an instrument for reinforcing state control and pandering to the elite. This is probably the biggest challenge decentralization is facing in Mozambique, therefore making it a fundamental issue to be taken into account in any reform in this area, within the context of strengthening democracy and promoting local development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Indicadores Básicos de Agricultura e Alimentação 2015-2019 - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística (INE), 2020)
1. Esta publicação apresenta os indicadores básicos de agricultura e alimentação dos últimos 5 anos, como alternativa da base de dados na plataforma online “countryStat” produzida com fontes administrativas, mas descontinuada em 2019. A publicação não abrange todos indicadores cobertos como desejado, porque alguns requerem harmonização metodológica e outros ainda não são produzidos com regularidade pelos sectores. 2. A compilação desta publicação baseou-se na recolha e tratamento preliminar das bases de dados disponibilizadas pelas fontes administrativas dos sectores. A seguir, a equipa de produção fez a limpeza e validação de dados, resultando na publicação com 10 grupos de indicadores. 3. Nos indicadores socio-demográficos, destaca-se a população de Moçambique, como principal activo da produção, ao atingir a magnitude de 29,3 milhões de habitantes em 2019, 66,2% da qual vivia na área rural, e continuando concentrada em Nampula e Zambézia com 6,03 e 5,43 milhões de habitantes respectivamente. 4. O segundo indicador refere-se à insegurança alimentar aguda, cujo resultado indica um grande agravamento, ao partir de 3,6% em 2013 para 29,9% de famílias em 2019, um comportamento assumido também pela desnutrição aguda em crianças que de 1,9% em 2013 deteriorou-se para 12,3% em 2019. 5. Nos indicadores económicos, ressalta o peso do PIB do sector agrário a preços constantes, ano base de 2014, que estabilizou-se em torno de 23%, entre 2015 e 2019, tendo a respectiva taxa de crescimento registado 1,2% em 2019, abaixo da média nacional que foi de 2,3% face a 2018. O orçamento do estado alocado ao sector continuou abaixo de 10% em todo quinquénio, tendo-se fixado em 4,9% em 2019 6. A mecanização agrícola, medida pelo número de tractores alocados pelo Fundo do Desenvolvimento Agrário ao sector privado para agricultura familiar, reduziu, ao partir de 361 em 2015 para 26 unidades em 2019. No entanto, a área lavrada pelos provedores deste serviço e os produtores beneficiados aumentaram 97% e 781% respectivamente entre 2015 e 2019. 7. O crédito concedido ao sector agrário manteve-se insignificante se comparado com o resto da economia ao corresponder a um peso de 3,65% em 2015 e 3,71% em 2019. 8. A produção per capita de cereais continuou baixa para garantir a segurança alimentar, ao registar 71(Kg/hab) em 2015 e 94,3 kg em 2019. Para mandioca e batata doce, a situação continuou bem e melhor com a produção per capita de 267 kg em 2015 e 336 kg em 2019. A produção das culturas de rendimento foi estável no período de referência, facto observado nas mudas de cajueiros produzidas em torno de 4,5 milhões em 2019. Os produtos pecuários apresentaram, ao longo do quinquério, valores per capita baixos. Com efeito, a carne de frango registou uma produção per capita de 3,8 kg em 2019, partindo de 2,5 kg em 2015. Na produção de carne bovina, destacou-se a Província de Maputo com quase a metade da produção do País, 7 266 toneladas em 2019. Manica e Sofala destacaram-se na produção de leite de vaca ao deter 41,3 % e 25,1 % do total em 2019, respectivamente. A produção de pescado per capita caiu para 11,6 em 2019, depois de 13,7 kg em 2018 e 12,4 kg em 2017. Contudo, ressalta-se a produção de peixe marinho com 177 071 toneladas em 2019 correspondentes a 59,5% de toda a produção do sector. 9. No comércio externo, evidencia-se a exportação de açúcar e produtos de confeitaria, com crescimento de 22,9% da contribuição na receita aduaneira de 2019.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - indicators / indicadores; Northern PEA; agriculture / agricultura

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Campanha Agrícola 20/21: Mais de 300 mil hectares lavrados na campanha agrícola 2020/21 - MADER (Agricultura, 2020)
Mais de 300 mil hectares lavrados na campanha agrícola 2020/21
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Análise do Plano Económico e Social e Orçamento do Estado de 2020 nas Áreas da Saúde, Água e Saneamento - Marrengula, Constantino (Forum de Monitoria do Orçamento, FMO Mais, PAANE, 2020)
Os objectivos e os pilares do PES e OE de 2020 não mudaram, substancialmente, em comparação com o que foram as prioridades do quinquênio 2015-2019. Em linha com os compromissos internacionais, o Governo procurou manter os pesos relativos da despesa nos sectores prioritários, com particular realce para a educação e a saúde. Contudo, o aumento dos preços e dos encargos da dívida, que se seguiu à descoberta das dívidas não declaradas, baixou o valor real das provisões feitas nestes sectores. O valor de cerca de 26 mil milhões de Meticais reservado para a saúde em 2020 representa uma redução em relação ao que tinha sido programado para 2019, não obstante os desafios impostos pela pandemia da Covid19. A redução em termos reais do orçamento da saúde, ocorre num quadro geral, em que todas as metas previstas para o quinquênio passado foram revistas em baixa, ou não foram cumpridas. Por exemplo, num ano eleitoral como foi 2019, a taxa de realização da meta de recrutamento de profissionais para o sistema nacional da saúde situou-se em volta de 50%. As metas do PES e OE 2020 da saúde não parecem suficientes para que o sector recupere dos incumprimentos do quinquênio passado, num contexto que conta com a pandemia da Covid-19. Para o sector de água e saneamento, os acordos assinados com o Exim Bank da Índia, o Banco Mundial, e a SADC deram um novo impulso ao Programa PRAVIDA, mas o nível de realização das metas do PES e do orçamento do sector não foi substancialmente diferente do que aconteceu na saúde. Quando o orçamento aumentou em 2019 a taxa de execução do orçamento baixou para 32%, com incumprimentos em intervenções com impacto directo na pobreza, tanto rural como na zona peri-urbana. A revisão em baixa das metas do PES de 2020, em comparação com o definido para 2019, alarga o tempo necessário para que a intervenção do Estado no sector faça a diferença no acesso à água e saneamento. Num cenário de crescimento populacional, quanto mais conservadora e lenta for a intervenção maior é o atraso na correcção dos problemas identificados, o que certamente tem implicações na materialização dos objetivos de desenvolvimento sustentável. Reverter o cenário que sustenta as taxas de execução sub-óptimas dos orçamentos aprovados e a queda em termos reais das disponibilidades nos sectores prioritários constitui o principal desafio das Finanças Públicas em Moçambique. Embora não esteja claro o que poderá ser o futuro destes sectores depois da pandemia da Covid-19, a curto prazo torna-se importante encontrar formas de usar melhor o que se tem, retomar a trajectoria de sustentabilidade da dívida pública e normalizar as relações com os principais parceiros de apoio orçamental. Como se pode perceber da dinâmica dos indicadores da saúde, água e saneamento, os custos sociais de sub-utilizar o potencial existente e manter o status quo nas Finanças Públicas são demasiado altos para serem desconsiderados.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health - WASH / saúde - água; higiene e saneamento; health / saúde

Cabo Delgado e o Risco Sistémico da Guerra em Moçambique - Ngoenha, Severino; do Amaral, Giverage; Nhumaio, Alcido (Desafios para Moçambique 2020, 2020)
Em Moçambique a guerra é um risco sistémico: na linguagem de Thomas Hobbes, é a mãe de todos os riscos. A guerra é transversal a todos os outros riscos em termos de consequências sociais, económicas, políticas e culturais: destrói as infra-estruturas, como a rede escolar, os hospitais, as vias de acesso e os tecidos sociais; enfraquece a economia; paralisa a agricultura; apodera-se da indústria; e instala a fome, a miséria e toda a espécie de desgraças. A guerra é o maior dos riscos sistémicos de Moçambique não apenas pelos seus efeitos altamente destrutivos, mas porque agrava a probabilidade de ocorrência dos demais riscos aos quais o País está sistemática e concomitantemente exposto. Em geral, as considerações sobre a guerra em Moçambique são feitas de duas maneiras diferentes. De um lado, a abordagem político-militar, que privilegia a busca de mecanismos de diálogo entre os beligerantes, o que supõe o conhecimento e o reconhecimento entre as partes e das razões que levam uns e outros a optar por um confronto armado. Esta abordagem tem sido a adoptada pelos diferentes governos moçambicanos que enfrentaram conflitos nos seus mandatos, ou seja, todos. Actualmente não parece que uma tal via se vislumbre salutar nas estratégias contra os dois conflitos armados em curso no Centro e Norte do País. Por outo lado, a abordagem técnico-científica, que parte do pressuposto de que o fenómeno da guerra é complexo e privilegia uma epistemologia interdisciplinar, na qual participam muitos saberes disciplinares no esforço de apreender as suas razões e causas. Esta abordagem procura entender o que leva o País a fazer da guerra o seu modus vivendi, o que leva grupos, partidos e facções militares a optarem sistematicamente pela confrontação militar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

O Cabo do Medo - O Daesh em Moçambique 2019-2020 - Rogeiro, Nuno (UCCLA, 2020)
Toda a verdade sobre a situação explosiva do domínio do Norte de Moçambique pelo Daesh. É o primeiro livro a nível mundial que revela em primeira mão o que se está a passar na zona de Cabo Delgado: a conquista e subjugação das populações, a violência bárbara com recurso a decapitações e execuções sumárias, a exploração das pessoas e dos recursos disponíveis, a impotência das autoridades moçambicanas em impor a ordem e a paz social. Um livro de grande acualidade que desvenda uma realidade tão chocante quanto desconhecida. “Uma análise exaustiva da ocupação desta terra boa (nordeste de Moçambique), de gente boa, pelo Daesh. Tem de ser combatido mas, primeiro, tem de ser compreendido.” Nuno Rogeiro
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Investimento Directo Estrangeiro e o Desenvolvimento Socioeconómico em Moçambique: Dinâmicas, Tensões e Desafios - Sambo, Michael Godet (Desafios para Moçambique 2020, 2020)
Considerando a estrutura económica de Moçambique e analisando a estrutura do IDE que aflui a Moçambique, este artigo argumenta que o aumento de IDE na economia não é necessariamente a condição para o desenvolvimento se não for maximizada a captação e utilização das receitas. Embora a lógica de fomento do desenvolvimento económico através do investimento adoptada pelo Governo de Moçambique no PQG 2015-2019 tenha um embasamento teórico, o seu enquadramento é simplista e pouco considera a natureza do investimento, o contexto em que este é aplicado e o seu efeito estrutural na economia. O argumento resulta, além da revisão bibliográfica e documental, de uma análise dos dados económicos oficiais de Moçambique, com destaque para os dados do IDE publicados pelo Banco de Moçambique, conjugados com a análise dos materiais de trabalhos de campo sobre o IDE na província de Nampula em 2016 e na Província de Gaza em 2019. O texto está estruturado em três partes além da introdução e conclusão. A primeira faz um enquadramento teórico da discussão, a segunda analisa as dinâmicas de IDE na economia e a terceira analisa algumas evidências empíricas dos efeitos socioeconómicos causados pelos projectos de IDE nas comunidades receptoras dos projectos.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português

State Budget Proposal for Fiscal Year 2020 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2020)
Key messages: 1. The value of the State Budget for 2020 is MT 345.4 b. The 2020 State Budget marks the beginning of a new governance cycle (2020-2024) and is aligned with the strategic objectives and priorities defined in the new 5-year plan (PQG 2020-2024). However, the current global COVID19-induced economic uncertainty has led the Government of Mozambique to a restrictive approach to the budget aimed at prioritizing the provision of basic services to the population. 2. The Council of Ministry’s Decree n.2/2020 established the principles and norms of the provincial decentralized governance, both political and financial. However, this was not yet reflected in 2020 State Budget. 3. The government’s new overarching development strategy, the “Government’s Five-Year Plan (PQG 2020-2024)” has 3 strategic priorities and 3 strategic pillars. In the 2020 State Budget, Priority II: Promote Economic Growth, Productivity and Job Creation, received the majority of funding, worth 44 percent of budget. Priority I: Develop Human Capital and Social Justice was allocated 35 percent of 2020 State Budget resources. 4. This year the Government has prioritized the allocation of resources to essential sectors, namely Health, Education and Agriculture & Rural Development. The allocation to these three sectors is worth 48 percent of 2020 State Budget (excluding debt servicing and financial operations) or 34 percent of the entire budget. Relative to last year, the allocation to the Education sector increased while those of the Health and Agriculture sectors decreased. 5. In the 2020-2024 PQG, the Government set the goal of allocating 65.2 percent of resources to priority economic and social sectors. This year’s cumulative allocation to priority areas is worth 68 percent of the State Budget less financial operations and debt servicing, or 48 percent of the entire State Budget including financial operations and debt servicing. Of the priority Economic and Social sectors supported by UNICEF, Education was allocated Meticals (MT) 66.3 billions (b), Health MT 26.7 b, Social Action MT 6.7 b and WASH MT 7.1 b in the State Budget for 2020. 6. The allocation to Education increased by 17 percent in nominal terms and by 9 percent in real terms relative to 2019 Budget. The sector allocation is worth 19.2 percent of 2020 State Budget. Excluding financial operations and debt servicing, education represents 27.1 percent. As a share of Mozambique’s GDP, the Education sector’ allocation represents 6.1 percent. 7. The Health allocation represents a 5 percent nominal decrease and an 11 percent real terms-decrease compared to last year’s budget. Such decrease is explained by the heavy reduction in externally-funded on-budget resources to the sector. Health is worth 7.7 percent of the 2020 budget. Excluding financial operations and debt servicing, the sector represents 10.9 percent. As a share of the expected GDP for 2020, the Health Budget is worth approximately 2.5 percent. Relative to last year, the sector allocations decreased both as a share of government expenditure and as a share of GDP. 8. The Ministry of Health has developed a National Plan for COVID-19 preparedness and response which will be allocated approximately MT 1.8 b or USD 28.4 m through off-budget resources, of which 56 percent will be allocated to drugs and supplies. The Ministry of Health COVID-19 Plan however does not include budget for water services and hygiene measures essential to Infection prevention and control (IPC). 9. The 2020 initial allocation to Social Action dropped by 7 percent in nominal terms and by 14 percent in real terms compared to 2019. However, spending for INAS Social Protection Programs as a share of budget and as a share of GDP is on par with those of last year. Still, given the risk of increased vulnerabilities due to COVID-19, larger allocations to INAS programs are recommended.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
OCLC: 1164631287
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Publisher: Institute for Security Studies (ISS)
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Coesão social e violência política em Moçambique: notas para debate - Forquilha, Salvador; Gonçalves, Euclides (2019)
Perguntas e método de pesquisa Contexto: • Dados da primeira fase de uma pesquisa programática no norte de Moçambique Pergunta: • Como operacionalizar operacionalizar a noção de coesão social em Moçambique? • Que subsídios a noção de coesão social pode oferecer para a compreensão da violência política em Moçambique? Recolha de dados • Período: Abril e Maio de 2019 • Locais: Cidade de Maputo, Chiúre (Cabo Delgado), Chimbunila (Niassa) e Mussuril (Nampula) • Entrevistas: Representantes e membros de partidos políticos, líderes comunitários e religiosos, grupos de camponeses e jovens • Análise de dados: Mapeamento de factores com potencial para conflicto (conflict mapping)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Conferência Internacional Sobre a Educação da Rapariga - ROSC (ROSC - Fórum da Sociedade Civil para os Direitos da Criança, 2019)
O Movimento de Educação para Todos (MEPT) em coordenação com o Ministério da Educação e Desenvolvimento Humano (MINEDH), realizou nos dias 6 e 7 de Junho do corrente ano, em Maputo, a Conferência Internacional Sobre a Educação da Rapariga com o lema “Desafios, Partilha de Experiências e Boas Práticas para Assegurar a Retenção da Rapariga no Sistema de Ensino.” Esta conferência tinha como objetivos: → Troca de experiências em torno de políticas e práticas existentes a nível nacional e internacional para assegurar a retenção da rapariga no sistema de ensino e discutir estratégias e possíveis soluções para a redução dos índices de abandono escolar por parte das raparigas na África Subsariana; → Apreciar os instrumentos e experiências existentes para prevenir a gravidez infantil e combater a violência baseada no género nas escolas a nível da região; → Olhar para os instrumentos e experiências existentes de boas práticas na região para o tratamento de casos de alunas grávidas nas escolas e a sua reintegração.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género

Tanzaniano recruta jovens no Niassa para ataques em Cabo Delgado - Governo de Moçambique (Governo de Moçambique, 2019)
Alguns jovens do distrito de Mecula, no Niassa, norte de Moçambique, são recrutados para integrarem o grupo de malfeitores que protagonizam ataques armados nos distritos do norte da vizinha província de Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Niassa; L - portuguese / português; youth / juventude

Input subsidies in Mozambique: The future of peasant farmers and their seed systems - Lewis, Linzi (African Centre for Biodiversity, 2019)
In this paper, we discuss and assess the input subsidy programmes in Mozambique, as part of the larger agriculture policy landscape, the impact this has had on the agricultural sector in Mozambique, and particularly on smallholder farmers. Input subsidy programmes in Mozambique are fragmented and operate more along the lines of projects and pilots. Therefore, this paper selects a few key projects to explore approaches being taken by the Mozambican government, along with international donors, providing agricultural inputs to peasant farmers. Notably we consider the more recent Food and Agriculture Organization (FAO)’s input subsidy programme, and the World Bank funded Agriculture and Natural Resources Landscape Management (SUSTENTA) programme/project, implemented by the National Sustainable Development Fund2 (FNDS), under the Ministry of Land, Environment and Rural Development (MITADER). This paper provides a brief background to agriculture in Mozambique, followed by the agricultural policies, plans and budgets guiding agricultural investments in the country. After briefly outlining the agricultural sector – notably seed, fertiliser and agro-dealers in the country – we discuss and analyse selected input subsidy programmes in Mozambique. The paper closes with a conclusion and recommendations to feed into future discussions with farmers, farmer organisations, non-governmental organisations (NGOs) and others in Mozambique.
978-0-6399760-4-4
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Subsídios em insumos em Moçambique: O futuro dos agricultores camponeses e dos seus sistemas de sementes - Lewis, Linzi (African Centre for Biodiversity, 2019)
Neste artigo, discutimos e avaliamos os programas de subsídios em insumos em Moçambique, como parte do panorama mais amplo da política agrícola, o impacto que estes têm tido no sector agrícola em Moçambique e particularmente nos pequenos agricultores. Os programas de subsídios em Moçambique são fragmentados e operam mais ao logo das linhas de projectos e pilotos. Este artigo selecciona, portanto, alguns dos projectos principais para explorar abordagens que estão a ser usadas pelo governo Moçambicano, juntamente com doadores internacionais, para fornecer insumos agrícolas aos produtores camponeses. Notavelmente consideramos o programa de subsídios em insumos mais recente da FAO (Organização para Alimentação e Agricultura), e o projecto/ Programa Agrícola e de Gestão de Paisagens de Recursos Naturais (SUSTENTA) financiado pelo Banco Mundial, implementado pelo Fundo Nacional de Desenvolvimento Sustentável (FNDS), debaixo do Ministério da Terra, Ambiente e Desenvolvimento Rural (MITADER). Este ensaio oferece um breve histórico da agricultura em Moçambique, seguido por políticas, planos e orçamentos agrícolas que guiam os investimentos agrícolas no país. Após brevemente esboçar o sector agrícola – nomeadamente os vendedores de sementes, de fertilizantes e de agroinsumos no país – – discutimos e analisamos programas seleccionados de subsídios em insumos em Moçambique. O artigo encerra com uma conclusão e com recomendações para contribuir para discussões futuras com agricultores, organizações de agricultores, organizações não-governamentais (ONGs) e outros em Moçambique.
ISBN: 978-0-6399760-5-1
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Resultados Definitivos: Censo 2017 - Instituto Nacional de Estatística - INE (2019)
O Censo foi realizado em todo o País de 1 a 15 de Agosto de 2017.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Publisher: Routledge
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

One-stop service policy as a bureaucratic reform in Indonesia - Umar, Akmal; Madani, Muhlis; Amrin; Farida, Umi; Yusriadi, Yusriadi; Elpisah; Bin Tahir, Saidna; Sakkir, Geminastiti (Academy of Strategic Management Journal, 2019)
Bureaucratic reform is an effort to improve the system of government administration, especially institutional aspects, management, and human resources of the apparatus. One of the bureaucratic reforms in Indonesia is the establishment of the One-Stop Service (OSS) office which handles and integrates all forms of licensing. This article examined how the implementation of public service reform and how the change of management practices had been implemented in the OSS of Bone Regency. Data were collected through a semi-structured interview with 16 of OSS' employees and nine service-users. This study applied a qualitative approach using a case study design. Techniques of data collection used three kinds of
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Cyclones Idai and Kenneth - OCHA (United Nations Office for the Coordination of Humanitarian Affairs, 2019)
In March and April 2019, Southern Africa was hit by two subsequent cyclones that left a trail of destruction in their path, and close to 2.2 million people in need urgent assistance in Mozambique alone. On the night of 14 to 15 March Tropical Cyclone Idai made landfall near Beira City, Sofala Province, in central Mozambique. The cyclone brought torrential rains and winds to Sofala, Zambezia, Manica and Inhambane provinces. Cyclone Idai continued across land as a Tropical Storm and hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. Idai left more than 600 people dead and an estimated 1.85 million people in need in Mozambique alone. On 24 April, Tropical Cyclone Kenneth passed north of the Comoros Islands, hitting the northern island of Ngazidja. On the evening of 25 April, the cyclone made landfall in Mozambique between the districts of Macomia and Mocimboa da Praia in Cabo Delgado province. With wind gusts of up to 220km/h, Tropical Cyclone Kenneth became the strongest cyclone to ever hit the African continent. Cyclone Kenneth left 374,000 people in need. Tropical Cyclone Kenneth reportedly caused three deaths, at least 20 injuries and extensive damage to houses across the archipelago. Preliminary estimates indicate that at least 1,000 people were displaced, most of them children. While assessments are ongoing, initial reports from the Comoros indicate that several villages were flooded due to sea surges and broken dykes, and that power was cut in multiple locations. Roads have reportedly been damaged and cut off by fallen trees, while telephone poles are down in multiple locations. Latest updates on the response can be found here. It is the first time in recorded history that two strong tropical cyclones have hit Mozambique in the same season. Cyclone Idai As of 9 April, the official death toll caused by Cyclone Idai stands at 602 people, with more than 1,600 people injured, according to the Government. Many people are displaced, and communicable diseases are on the rise. Of particular concern are cholera and malaria. An oral vaccination campaign reached over 800,000 people by early April 2018. Many schools are damaged or used as shelter for displaced people. Humanitarian partners continue to call for any relocations out of schools or elsewhere to be safe, dignified and voluntary. In figures People in need 1.85M People targeted 1.72M Funding needed $282M Cyclone Kenneth The cyclone hit Mozambique more north than Cyclone Idai, with Quissanga, Macomia, and Ibo districts in Cabo Delgado hardest-hit, according to preliminary government reports. At least 45 deaths have been reported and 18,029 people were initially reportedly displaced, according to the National Disaster Management Institute (INGC). Cyclone Kenneth made landfall at the end of the rainy season, when river levels were already high, increasing the risk of river flooding. Humanitarian needs in Mozambique have sky-rocketed, and the humanitarian response will need to rapidly scale-up while capacity and funding are limited. In figures People in need 374K People targeted 374K Funding needed $104M On 16 March, Cyclone Idai hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. The homes of at least 4,000 households are destroyed or currently uninhabitable. The seven districts affected by Cyclone Idai- Chipinge, Chimanimani, Buhera, Bikita, Mutare, Gutu, and Chiredzi - multisectoral support will be required to speed recovery. The livelihoods of over 270,000 people across these districts has been affected. Those lviing in Chipinge and Chimanimani districts are worst hit. In early March, heavy rains and flooding linked to Cyclone Idai killed 60 people, displaced nearly 87,000 people and affected nearly 870,000 persons. The Government of Malawi declared a ‘state of disaster’ on 8 March and subsequently launched a Flood Response Plan and Appeal on 28 March to support life-saving humanitarian interventions in 15 affected districts. Humanitarian partners and the Government of Malawi have reached over 400,000 persons with immediate life-saving relief support which includes food, medicine, shelter, protection services and other non-food-items such as water, sanitation and hygiene supplies. A Post Disaster Needs Assessment (PDNA) has been undertaken by the Malawi Government, UN, World Bank and European Union to assess damages, losses and priority recovery needs and costs. The data and information collected will inform the Government’s recovery plan.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; natural disasters / desastres naturais

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

Recent evidence of the development of micro, small and medium enterprises in Indonesia - Tambunan, Tulus (Journal of Global Entrepreneurship Research, 2019)
This paper examines the development of micro, small and medium enterprises (MSMEs) in Indonesia. It has three research issues, namely the role of MSMEs, their constraints, and the importance of MSMEs for the creation of business opportunities for women. More specifically, the study aims to answer the following research questions. First, how important are MSMEs in Indonesia? Second, what are their main constraints? Third, how important are they, especially micro and small enterprises (MSEs), for the creation of business opportunities for women? Fourth, is the growth of MSEs a sign of increased entrepreneurial spirit or a reflection of poverty? This study adopted descriptive analysis using secondary data. It shows that MSMEs in Indonesia are dominated by MSEs, and accounted for almost 100% of all existing firms but only contributed between 58 to 61% of gross domestic product (GDP). About 42.84% of MSEs are owned by women, although the ratio of female to male entrepreneurs in MSEs varies by province. Poverty seems to be the main force behind the growth of MSEs. This study ends with some policy recommendations that the government should: (i) conduct trainings that focus on online marketing, entrepreneurship, management, and improving the quality of product and business efficiency; (ii) provide alternative funding facilities with low interest rates and non-burdensome requirements; and (iii) provide assistance directly in the production site for new entrepreneurs in their first years of running businesses. In addition, all gender discrimination treatments that have been burdensome for women to run own businesses must be eliminated. This study has, however, several limitations, especially with respect to the third and fourth research questions. Secondary data used does not have information about the main/initial motivation of MSME owners to run their own business and their socio-economic profiles.
Number: 1
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Transition from Civil War to Peace: The Role of the United Nations and International Community in Mozambique - Adedokun, Ayokunu (Peace and Conflict Studies, 2019)
With the heavy involvement of the United Nations (UN) and the international community, the Rome General Peace Agreement of 1992 ended more than 16 years of civil war in Mozambique. The peace agreement and post-conflict initiatives by the international community was successful in transforming the Mozambique National Resistance (Renamo) from a rebel group into a viable political party. Key components of the United Nations and the broader international community success in negotiating peace and creating conditions for political stability and democracy in Mozambique were (a) the provision of disarmament, demobilization and reintegration (DDR) before democratisation, (b) decentralization of humanitarian and relief efforts to provincial and district levels, (c) provision of financial support directly for the development of political parties, and (d) budget support to sectors relevant to peacebuilding. Though imperfect, Mozambique remains an important case study in how the UN and international community can help in post-conflict environments. Thus, the paper argues that success in peacebuilding operations depends on credible and impartial international support through the UN, as opposed to peacebuilding operations through the United States of America or Russia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Anuário Estatístico - Statistical Yearbook 2018 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2019)
À semelhança das edições anteriores, o Anuário Estatístico 2018 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Representação Comunitária na Gestão de Terras e Recursos Naturais. Nota Técnica - Salomão, Alda; Mário, T. V.; Tanner, Christopher (SPEED+; USAID, 2019)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

The Political Economy of Social Protection in Mozambique - Buur, Lars; Salimo, Padil (SSRN Electronic Journal, 2018)
In the view of international donors, multilateral organisations and government officials, social protection in Mozambique benefits from strong government commitment to it. Their argument is that, in contrast to many African countries, the government has demonstrated a level of commitment and support to social protection that is quite unprecedented. This view relies on the fact that more than 90 per cent of the budget allocated to the implementation of social protection programmes comes from the state budget and that, even within the complex context of the financial crisis that has devastated the economy since 2013, social protection has continued to receive special attention from the government in its budget allocations. Based on a political economy analysis, this paper challenges the common narrative of social protection in Mozambique, by arguing that social protection has been used as a means to mobilise resources from international agencies, in order to ensure the political survival of the Frelimo government. The paper argues that government support of social protection emerged as a reaction to the poor performance of poverty-reduction initiatives, becoming also a mechanism to overcome social protests after the 2008 and 2010 riots in Mozambique, which threatened to jeopardise the stability of the regime and its reproduction of power.
Keywords: *indexed; *tagged; Ethnographic Studies; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Social Protection PEA; development partners / parceiros de cooperação; social protection / proteção social

O processo de empoderamento das raparigas em Marrere - Estudo de caso do Projeto Mwarusi - Eloisa Nair Lopes da Costa (Instituto Universitário de Lisboa, 2018)
Desde o Acordo Geral de Paz, assinado em 1992, Moçambique realizou reformas políticas de intervenção no combate à pobreza. Contudo, em 2006, verificou-se que 54% da população moçambicana ainda se encontrava abaixo da linha de pobreza. Foi então que, Moçambique, em parceria com organizações internacionais iniciou os seus esforços na promoção de programas centrados na igualdade e equidade de género e a sua atuação junto de comunidades mais vulneráveis, tendo em conta particularmente a educação e a saúde. Para estes avanços contribuíram os Objetivos de Desenvolvimento do Milénio e o Plano de Ação para a redução da pobreza absoluta. O estudo de caso desenvolvido nesta dissertação tem como objetivo compreender o modo pelo qual o Projeto Mwarusi, implementado pela Girl Move Foundation, contribui para um empoderamento efetivo das raparigas no bairro de Marrere em Nampula, Moçambique, compreender o seu impacto na comunidade e a sua aplicabilidade a outras comunidades e grupos. Para compreender o Projeto Mwarusi e, em particular, a situação da mulher moçambicana e as políticas de promoção de igualdade, equidade e empoderamento existentes em Moçambique, foi necessário realizar-se uma análise multivariada que nos permitiu obter um conhecimento não só teórico, ao nível das perspetivas em questão, como prático que nos deu a oportunidade de conhecer a comunidade, a sua cultura e as suas tradições. Esta investigação tem, então, como objetivo a análise do Projeto Mwarusi, através de uma observação participante ao longo das sessões do projeto, através da realização de entrevistas semiestruturadas e questionários on-line aplicados a seis guias, a oito mentoras do Projeto Mwarusi, o que nos permitirá avaliar o sucesso e impacto do Projeto Mwarusi e, por último, através do acompanhamento do desenvolvimento do projeto entre 2015 e 2018.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; empowerment / empoderamento; gender / género; youth / juventude

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
978-1-78118-441-7
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Radicalização Islâmica No Norte De Moçambique: O Caso Da Mocímboa Da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (2018)
Contextualização da pesquisa: - No dia 5 de Outubro de 2017, um grupo de homens armados, aparentemente com motivações religiosas, ataca instituições do Estado (postos policiais) na Vila da Mocímboa da Praia; - Rapidamente, o assunto da radicalização islâmica no norte de Moçambique passou a chamar a atenção do Governo, sector privado, sociedade civil, parceiros de cooperação, analistas, comentadores, cidadãos comuns, etc. - Para muita gente, as perguntas comuns eram: De onde vem esse grupo da Mocímboa da Praia? Existe fundamentalismo islâmico em Moçambique? Não são homens da Renamo disfarçados de fundamentalistas islâmicos? - Foi neste contexto que o IESE e o MASC decidiram realizar uma pesquisa exploratória como preparação para uma pesquisa mais aprofundada.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Livelihood Interventions and Biodiversity Conservation in Quirimbas National Park - Chevallier, Romy (South African Institute of International Affairs (SAIIA), 2018)
Coastal livelihood interventions can help communities by providing additional incomes, while protecting and maintaining resources and the environment. The identification and promotion of resilient and diversified livelihood opportunities are crucial to enhance communities’ adaptive capacity to respond to the multiple stresses and shocks in a changing coastal environment. Coastal livelihood opportunities are especially important in their support for biodiversity conservation in and around protected areas. Quirimbas National Park (QNP) in Mozambique has some of the greatest marine biodiversity in the region and is one of the country’s largest and most important protected areas. This policy insight considers the most appropriate livelihood-focused interventions for coastal communities in the QNP, taking account of past and current project experiences. In areas where communities and park officials need additional support, it makes recommendations on how to best enhance initiatives.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources / recursos naturais

Contract farming for improving smallholder incomes: What can we learn from effectiveness studies? - Ton, Giel; Vellema, Wytse; Desiere, Sam; Weituschat, Sophia; D'Haese, Marijke (World Development, 2018)
Contract farming is a sales arrangement between a farmer and a firm, agreed before production begins, which provides the farmer with resources or services. Many governments and donors promote contract farming as part of agricultural development policies. However, there is serious concern whether smaller farmers can benefit from these arrangements. This paper presents the results of a systematic review that analysed the evidence in the literature on income effects for smallholders. The review included all studies with an econometric design to reduce selection bias in effect estimates. The meta-analysis covered 26 empirical instances of contract farming in 13 developing countries. The contracts varied widely, with varying service packages provided by the firm to the farmers. Using truth table analysis, we explored combinations of services associated with relatively high or relatively low income effects. The meta-analysis resulted in an overall pooled average effect size of 38%. However, we show that there are publication and survivor biases. Non-significant effects are systematically underreported. Moreover, all studies assessed the effectiveness of the contractual arrangement when these had already survived the start-up problems. Both sources of bias lead to an overestimation of the average income effect. The findings point to the need for substantial income effects for contract farming arrangements to survive over time. Both firms and farmers face risks; for example, farmers may side-sell products after having received the services from the firm. The most effective contractual arrangements included a price premium, especially when there was no farmers’ organisation to broker the contract between the farmer and the firm. We show that smallholders can benefit from the contractual arrangement. However, the poorest farmers are rarely included; we show that, in 61% of the cases, the contract farmers had significantly larger landholdings or more assets than the average farmers in the region.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture - agricultural markets / agricultura - mercados agrícolos; agriculture / agricultura

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Accepted: 2018-05-01T10:02:21Z Publisher: Institute of Development Studies
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

The Impact Analysis of ASEAN-Japan Comprehensive Economic Partnership (ajcep) for Trade Flow and Economic Growth’s Convergence - Darsono, Tri Arifin; Hakim, Dedi Budiman; Rindayati, Wiwiek (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2018)
Free Trade Area (FTA) between ASEAN and Japan, which is called ASEAN-Japan Comprehensive Economic Partnership (AJCEP), has been established since 2002 as goods and services flow gateway. AJCEP plays an important role to bring the development, economic security, and economic power. It can also boost the economic growth among member of ASEAN-Japan. The objectives of this research were to analyze the factors that can influence the ASEAN-Japan countries import with non-member, to analyze the occurrence of trade creation and trade diversion in trading sector among ASEAN-Japan countries with non-member, and to analyze the occurrence of economic growth's convergence in ASEAN-Japan Comprehensive Economic Partnership (AJCEP) not only among ASEAN-Japan countries, but also with non-member trading partners. The Gravity Model was used to analyze import factors and observing the occurrence of trade creation or trade diversion. The GMM model was used to observe the convergence of economic growth. The research are used Panel data methods with periods 2000 until 2013 in 13 countries. The research found that the coefficient values in trade creation and trade diversion dummy were 0.92 and 31.41. The positive value in trade creation and trade diversion indicated the occurrence of trade creation in the import flow among ASEAN-Japan countries and non-member trading partners, as well as finding the convergence of economic growth among ASEAN-Japan countries. The convergence level was of 0.0153417 can be interpreted that the velocity to reach steady state condition was 2.00 percent per year with the assumption of ceteris paribus. The duration to reach convergence condition or half life of convergence was about 34 years. The research found the trade creation from AJCEP agreement and the occurrence of economic growth’s convergence. Based on the result, Indonesian government would likely to make relationships among countries member and non-member to invest in real sector that will boost economic growth in Indonesia. Keywords: ASEAN-Japan Comprehensive Economic Partnership, Growth’s convergence, gravity model, GMM model, trade creation, trade diversion.
Section: Articles
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Elite Bargains and Political Deals Project: Mozambique Case Study - Vines, Alex (UK Government Stabilisation Unit, 2018)
This case study is one of a series commissioned to support the Stabilisation Unit’s (SU) development of an evidence base relating to elite bargains and political deals. The project explores how national and international interventions have and have not been effective in fostering and sustaining political deals and elite bargains; and whether or not these political deals and elite bargains have helped reduce violence, increased local, regional and national stability and contributed to the strengthening of the relevant political settlement. Drawing on the case studies, the SU has developed a series of summary papers that bring together the project’s key findings and will underpin the revision of the existing ‘UK Approach to Stabilisation’ (2014) paper. The project also contributes to the SU’s growing engagement and expertise in this area and provides a comprehensive analytical resource for those inside and outside government
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; decentralization / descentralização; electoral geography / geografia eleitoral

Dinâmicas e dilemas do emprego, trabalho e bem-estar nas agro-indústrias florestais em Niassa - Ali, Rosimina (Emprego e transformação económica e social em Moçambique, 2018)
O artigo argumenta que o tipo de emprego que é gerado nas agro-indústrias florestais em Niassa reflecte o modo de organização produtivo prevalecente, no qual a base de rentabilidade das empresas está assente no pagamento de salários baixos e em condições sociais de trabalho precárias, sendo os trabalhadores responsáveis pela sua própria reprodução social. A reprodução social da força de trabalho, dadas as estruturas produtivas e de acumulação prevalecentes, é garantida pela interdependência de diversificadas formas de trabalho, remuneradas e/ou não remuneradas, quer agrícolas ou não. Nos moldes actuais de organização da produção e do trabalho, o emprego nas plantações florestais é maioritariamente casual, instável e inseguro, e desenvolve-se num contexto de tensões e contradições nas relações sociais produtivas. As precárias condições laborais têm implicações na disponibilidade e no tipo de força de trabalho que é gerada, nas condições da sua reprodução e produtividade bem como na sustentabilidade da estrutura produtiva prevalecente, na medida em que o trabalho é estruturado (e estrutura as) pelas estruturas produtivas. Este artigo está organizado em seis secções. A segunda secção olha para as dinâmicas do trabalho na província do Niassa e nos distritos em análise, com enfoque na ligação entre o trabalho assalariado, a agricultura familiar e a crise económica em Niassa. Segue-se, a terceira secção, que apresenta um breve panorama do desenvolvimento das indústrias florestais em Niassa e sua ligação com a situação do trabalho na província. A quarta secção analisa a organização produtiva do trabalho, os padrões e condições de emprego nas agro-indústrias florestais. Posteriormente, na quinta secção, descreve-se a experiência laboral e explica-se qual tem sido o impacto deste trabalho para o bem-estar dos trabalhadores e suas famílias. Essa experiência explica, em parte, tanto o descontentamento dos trabalhadores com o emprego criado, como as reclamações feitas pelas empresas sobre o trabalho. A sexta secção conclui, reflectindo sobre a necessidade de transformação dos moldes actuais de organização produtiva e do trabalho e avança algumas questões a enfrentar.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Education Service Delivery in Mozambique: A Second Round of the Service Delivery Indicators Survey - Bassi, Marina; Medina, Octavio; Nhampossa, Lúcia (World Bank, 2018)
This report presents the findings of the second round of the Service Delivery Indicators Survey (SDI) in Mozambique. The SDI analyses the performance of the education sector by assessing the quality of service delivery at the school level. SDI has been implemented in nine countries in Africa, including Mozambique in 2014.5 The study includes a set of indicators that measures teachers and principals’ ability and effort, as well as the availability of key inputs and resources that contribute to the functioning of a school. These metrics enable education authorities and schools to identify gaps and track progress over time (and across countries). The analysis is centered around three main questions: what do providers know? (teacher ability), what do providers do? (teacher effort), and what do providers have to work with? (input availability).
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; education / educação

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (World Bank, Washington, DC, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude

Elevating Indonesia's Performance in Ease of Doing Business Index (Policy Reforms to Improve the 'Starting a Business' Indicator) - Freddy, Imelda Magdalena; Saputri, N. (2018)
Indonesian President Joko Widodo has set a target of improving the country’s ranking in The World Bank’s Ease of Doing Business (EODB) index from 72nd to 40th by 2019. One barrier to meeting this challenge is Indonesia’s ranking in the Starting a Business Indicator, where it is 144th among 190 countries. According to the EODB Report, it takes 23 days and 11 procedures to register a business in Indonesia. To address this problem, the central government has implemented changes requiring parallel procedures with local governments and introduced a program called the Online Single Submission system (OSS), established in July 2018. However, there are major barriers to the success of these changes, including a lack of information for businesses, inadequate IT infrastructure, and failure to synchronize the central and local governments under the OSS. As a result, policy changes and the OSS have not been working as intended. Case studies in Jakarta, Bandung, and Bandar Lampung revealed that there are two regulations—one implemented by the local government and the other implemented by the central government—that should be revised to speed up business registration. The government should also remove a procedure from the business registration process and develop collaboration with local private sectors and business associations to improve the OSS. These changes would reduce the time required for registering a business by 17 days. These reforms would benefit small and medium businesses the most, since they are the most common types of business in Indonesia (approximately 98% of all businesses). Such a reduction in the time required to register a business would be enough to improve Indonesia’s Starting a Business Indicator ranking from 144th to 75th. Based on our findings, we recommend four policy changes. First, the Jakarta provincial government should revise the Regulation of the Head of Investment and One Stop Integrated Services 23/2017 Article 2d. The Mandatory Labor Affairs Report (MLAR) stipulated in this regulation should be removed as a business registration requirement. Its content is duplicates data provided by the BPJS Ketenagakerjaan documents as part of national social security program. In addition, requiring an MLAR contradicts the regulation of the Minister of Manpower (MOM) 14/2006, which says it is not required for business registration. Second, Government Regulation 24/2018 Article 78 should be reformed to require that the central government collaborate with local business associations to disseminate information about the OSS. This collaboration will ensure that information reaches even remote areas. Third, Government Regulation 24/2018 Article 88 should be reformed to ensure that the ministries related to the OSS assist local governments to synchronize standard operating procedures and regulations to implement the OSS. This assistance should continue for one year, after which there should be a penalty for local governments that fail to comply with the new procedures for registering businesses through the OSS. Fourth, Government Regulation 24/2018 Article 91 should be changed to ensure the government will collaborate with the private sector to improve the IT infrastructure in all regions to support the OSS. Participation by the private sector is important because they have the resources to provide internet access and computers needed to implement the OSS in districts and municipalities across Indonesia.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Empregados do Quintal (male domestic workers) in Nampula City: Domestic work, masculinities and matrilinearity - Humbane, Jossias Helder Jamisse (2018)
This study questions why domestic work that is generally considered a feminine job is yet a field dominated by men in the city of Nampula, Mozambique. In the attempt to explain this phenomenon, the research explores economic, social and cultural aspects. Due to the fact that Nampula is a province with a strong Islamic presence and the majority of the population identify themselves as belonging to the Makhuwa ethnic group—which is traditionally defined by a matrilinear kinship system—I argue that the domestic sector remaines masculinised because of the influence of the matrilinear values and gendered practices. I also argue that the Islamic patriarchal values play a decisive role as men see themselves as the exclusive family providers and for that reason forbid their wives to develop and to get engaged in economic activities outside the household. This study also explores notions of masculinity in connection with domestic work and examines how male domestic workers, coming from rural areas and employed in the city, perceive and perform their masculine identities. How does the job of the domestic worker shape particular understandings of masculinity? Given the fact that many domestic workers in Nampula are immigrant people from the rural areas of the Zambézia province, I argue that migrating and working in the city is considered as a way to achieve a manhood as immigrants have access to goods that can only be purchased in urban contexts and are scarce in the villages. The access to all these “modern” commodities and the experience of the city make the immigrant young boys to gain respect in their original communities.
Accepted: 2019-04-12T09:43:27Z Publisher: University of the Western Cape
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; employment / emprego; gender / género

Anuário Estatístico - Statistical Yearbook 2017 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2018)
À semelhança das edições anteriores, o Anuário Estatístico 2017 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Falta de alimentos agrava-se em zonas atacadas na província de Cabo Delgado - Macuácua, Amandio Roberto (Jornal Notícias, 2018)
A falta de alimentos está a agravar-se em zonas do interior na província de Cabo Delgado por causa dos ataques causados por grupos armados que têm levado a população a abandonar terras, alerta um relatório ontem divulgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

The Importance of Lender-borrower Relationships to the Availability of Small and Micro Credit: Case Study on Indonesian Kredit Usaha Rakyat Loans - Suryani, Embun (International Journal of Economics and Financial Issues; Mersin, 2018)
This study aims to examine how the relationships between a borrower and his potential lender affect the decisions of potential lender whether or not to provide or extend funds to the borrower. The author explores the available literature and original fieldwork to create a framework to capture this relationship. The study employs descriptive qualitative data to analyze and examine the research questions. The result shows that borrowers who build their commercial transactions with their lender on intensive relationships are more likely to receive and extend loans. The relationship effects arise because it motivates both lender and borrower to share private resources and facilitate access to loan opportunities, but does not influence the price of loans. To sum up, the lender-borrower relationships are valuable and seem to operate through quantities, trust and the length of these relationships. Furthermore, these relationships are more appropriate to be implemented for small and micro-lending.
Number: 4 Num Pages: 1-9 Place: Mersin, Turkey, Mersin Publisher: EconJournals Section: Articles
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

The Performance of Indonesia’s Public Credit Guarantee Scheme for MSMEs: A Regional Comparative Perspective - Tambunan, Tulus T.H. (Journal of Southeast Asian Economies, 2018)
Access to finance has been a key constraint for Indonesia’s micro, small and medium enterprises (MSMEs) that lack tangible assets to be used as collateral. Consequently, credit guarantee schemes (CGSs) are important instruments to meet MSMEs’ financial needs. This paper examines the effectiveness of the KUR (community business credit), a partial public CGS in Indonesia, by comparing it with similar schemes in other ASEAN member states (AMS). The findings suggest that the KUR programme, despite its limited coverage, has been quite effective throughout the country. Some of the critical factors behind its success include: wide dissemination of the programme; simplicity of the application procedure; full participation and support from banks; and strong coordination between all stakeholders.
Number: 2 Publisher: ISEAS - Yusof Ishak Institute
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Accepted: 2018-04-13T12:59:17Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Analysis Banking Role to Performance Improvement on Indonesia Small Medium Enterprises - Hedwigis (EUROPEAN RESEARCH STUDIES JOURNAL, 2017)
This study aims to analyze the role of banks to increase small and medium enterprises and economic growth in Yogyakarta province, Indonesia. The focus of this study examines how the role of banks in terms of lending to small and medium enterprises, credit to the private sector and its impact on economic growth in Yogyakarta Province. The data used in this research is secondary data obtained from the Central Bureau of Statistics.
Number: Issue 3A
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

No Niassa, jovens consomem cada vez mais álcool de forma excessiva - Deutsche Welle (DW.COM, 2017)
Na província do norte de Moçambique, muitos adolescentes e jovens entregam-se ao vício por falta de ocupação profissional.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; employment / emprego; youth / juventude

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Following the donor-designed path to Mozambique’s US$2.2 billion secret debt deal - Hanlon, Joseph (Third World Quarterly, 2017)
Strenuous efforts by donors and lenders over four decades turned Mozambique from a socialist success story into a neoliberal capitalist one. The private sector dominates; a domestic elite dependent on foreign companies has been created.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Colonial State Formation Without Integration: Tax Capacity and Labour Regimes in Portuguese Mozambique (1890s–1970s) - Alexopoulou, Kleoniki; Juif, Dácil (International Review of Social History, 2017)
Abstract Samir Amin (1972) divided the African continent into three “macro-regions of colonial influence” with distinct socio-economic systems and labour practices: Africa of the colonial trade or peasant economy, Africa of the concession-owning companies, and Africa of the labour reserves. We argue that Mozambique encompassed all three different “macro-regions” in a single colony. We reconstruct government revenue (direct/indirect taxes) raised at a district level between 1930 and 1973 and find persisting differences in the “tax capacity” of the three regions throughout the colonial period. The tax systems, we claim, developed in response to existing local geographic and economic conditions, particularly to labour practices. Portuguese colonial rule adapted to and promoted labour practices such as migration and forced labour to maximize revenue. The extent to which the lack of integration played a role in the post-colonial state and fiscal failure should be studied further. , TRANSLATED ABSTRACTS FRENCH – GERMAN – SPANISH Kleoniki Alexopoulou et Dácil Juif. Formation d’un État colonial sans intégration: la capacité fiscale et les régimes de travail au Mozambique portugais (1890-1970) . Samir Amin (1972) a divisé le continent africain en trois “macro-régions d’influence coloniale” dotées de systèmes socio-économiques et de pratiques de travail distincts: l’Afrique du commerce colonial ou de l’économie paysanne, l’Afrique des sociétés propriétaires de concessions et l’Afrique des réserves de main d’œuvre. Nous soutenons que le Mozambique a englobé toutes les trois “macro-régions” différentes dans une seule colonie. Nous reconstruisons les recettes publiques (impôts directs/indirects) prélevées au niveau du district entre 1930 et 1973, et nous relevons des différences persistantes dans la “capacité fiscale” des trois régions durant toute la période coloniale. Les systèmes fiscaux, selon nous, se sont développés en réponse à des conditions géographiques et économiques locales, et particulièrement à des pratiques de travail. La règle coloniale portugaise s’est ajustée à et a encouragé certaines pratiques de travail, telles que la migration et le travail forcé, afin d’optimiser les revenus. Le point auquel le manque d’intégration a joué un rôle dans l’État post-colonial et l’échec fiscal devraient faire l’objet d’études plus approfondies. Traduction: Christine Plard , Kleoniki Alexopoulou und Dácil Juif. Koloniale Staatsformierung ohne Integration: Steuerkraft und Arbeitsregime im portugiesisch regierten Mosambik (1890er bis 1970er Jahre). Samir Amin (1972) hat den afrikanischen Kontinent in drei “Makroregionen kolonialen Einflusses” mit je eigenen sozioökonomischen System und Arbeitspraktiken unterteilt: das Afrika des Kolonialhandels oder der kleinbäuerlichen Wirtschaft, das der über Konzessionen verfügenden Konzerne und das der Arbeitskräftereserven. Wir vertreten die These, dass Mosambik alle drei “Makroregionen” in einer einzigen Kolonie verband. Wir rekonstruieren die Einnahmen aus direkten und indirekten Steuern, die dem Staat zwischen 1930 und 1973 auf der Bezirksebene entstanden sind, und konstatieren, dass es während der Kolonialzeit anhaltende Differenzen in der “Steuerkraft” der drei Regionen gab. Die Steuersysteme entwickelten sich, so argumentieren wir, in Reaktion auf die lokal gegebenen geografischen und wirtschaftlichen Bedingungen, insbesondere in Reaktion auf die jeweiligen Arbeitspraktiken. Die portugiesische Kolonialherrschaft passte sich Praktiken wie der Migration und der Zwangsarbeit an und förderte sie, um die eigenen Einnahmen zu maximieren. Inwiefern der Mangel an Integration für den postkolonialen Staat und dessen fiskalisches Versagen eine Rolle gespielt hat, sollte noch näher untersucht werden. Übersetzung: Max Henninger , Kleoniki Alexopoulou y Dácil Juif. La formación de un estado colonial sin integración: capacidad impositiva y regímenes laborales en el Mozambique Portugués (1890-1970) . En 1972 Samir Amin dividió el continente africano en tres “macroregiones de influencia colonial” con unos sistemas socioeconómicos y unas prácticas laborales distintas: el África del comercio colonial o de la economía campesina, el África de las empresas propietarias de concesiones, y el África de las reservas de trabajo. En el artículo consideramos que Mozambique abarca esos tres tipos diferentes de macroregiones en una sola colonia. En él realizamos una reconstrucción de los ingresos (tanto de los impuestos directos como de los indirectos) recaudados por el gobierno a nivel regional entre 1930 y 1973. Encontramos diferencias continuadas en la “capacidad impositiva” de las tres regiones a lo largo del periodo colonial. Consideramos que el sistema de impuestos se desarrolló en respuesta a las condiciones geográficas y económicas existentes a nivel local, particularmente en lo que se refiere a las prácticas laborales. La legislación colonial portuguesa adaptó y promovió unas determinadas prácticas de trabajo tales como la migración y el trabajo forzado para conseguir una maximización de los ingresos impositivos. Las implicaciones de esta falta de integración jugaron un papel destacado en el estado post-colonial y en su quiebra fiscal; un aspecto que deberá ser estudiado con mayor profundidad. Traducción: Vicent Sanz Rozalén
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Anuário Estatístico - Statistical Yearbook 2016 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2017)
O Anuário Estatístico 2016 é parte da série de publicações que o Instituto Nacional de Estatística leva aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2012-2016. O ano de 2016 foi crucial no âmbito da preparação do IV Recenseamento Geral da População e Habitação 2017. Seguindo as recomendações internacionais, em Outubro teve lugar o Censo Piloto, onde foi testada toda a máquina e produzidos os devidos ajustamentos metodológicos rumo ao Censo 2017.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

O agronegócio no desenvolvimento do meio rural em Moçambique: perceção e análise das cadeias de valor de milho e da mandioca na província de Nampula - Linha, Paulo (Universidade de Lisboa, 2017)
O Agronegócio em Moçambique poderá ser um factor dinamizador da agricultura, chave para o desevolvimento económico, elemento para a equidade no desenvolvimento social e fundamental para a redução da pobreza e da fome. O estudo analisa as perceções dos atores do agronegócio do milho e da mandioca sobre o impacto destas culturas na vida económica e social no meio rural. Diante desta perspetiva, esta pesquisa teve como objetivo investigar prospectivamente as cadeias de valor das culturas do milho e da mandioca, no corredor de Nacala, com vista a identificar formas de potenciar o desenvolvimento do agronegócio como fator dinamizador da promoção do desenvolvimento socioeconómico sustentável no meio rural. Os resultados alcançados indicam que em Moçambique, de forma geral, o agronegócio do milho e da mandioca é potencial pilar dinamizador que poderá contribuir para o desenvolvimento da agricultura e impulsionar o crescimento económico e o desenvolvimento social se o Estado colocar-se na dianteira na criação, nas zonas de produção, de infraestruturas públicas para a prática de uma agricultura economicamente sustentável e uma legislação flexível e promotora de um clima propício para o agronegócio. Com as infraestruturas públicas criadas nos centros de produção deve-se optar, pelo envolvimento de todos atores do agronegócio num sistema de Integração e Coordenação Vertical, apostando na transformação da baixa renda da agricultura rural em agricultura comercial e competitiva para que efetivamente o agronegócio seja um dos pilares para o combate da fome e da pobreza no meio rural. A Integração e Coordenação Vertical, significa a existência de instituições âncoras que se dedicam a puxar a atividade do agronegócio dos produtores locais na base contratual. Esta forma promete rápida integração ao mercado, crescimento económico, inovação tecnológica, ao mesmo tempo em que protege os direitos e a autonomia do produtor sob regime de integração e coordenação. Agribusiness in Mozambique could be a driving force for agriculture, key to economic development, an element for equity in social development and fundamental to reducing poverty and hunger. The study analyzes the perceptions of corn and cassava agribusiness actors on the impact of these crops on economic and social life in rural areas. The objective of this research was to investigate prospectively the corn and cassava value chains in the Nacala corridor in order to identify ways to promote the development of agribusiness as a driving force for the promotion of sustainable socioeconomic development in the environment rural. The results indicate that, in general, corn and cassava agribusiness in Mozambique are potential pivotal factors that could contribute to the development of agriculture and boost economic growth and social development, if the government takes the initiative to build public infrastructures for an economic sustainable agriculture as well as create a flexible legislation that promotes a proper environment for agribusiness. With the public infrastructures created in the production centers, one must opt for the involvement of all agribusiness actors in a system of Integration and Vertical Coordination, betting on the transformation of low income from rural agriculture into commercial and competitive agriculture so that agribusiness is effectively a pillar to combat hunger and poverty in rural areas. Integration and Vertical Coordination means the existence of anchor institution dedicated to pull the agribusiness activity of the local producers in the contractual basis. This form promises rapid market integration, economic growth, technological innovation, while protecting the rights and autonomy of the producer under integration and coordination.
Accepted: 2018-04-09T13:15:08Z
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; agriculture / agricultura; private sector / setor privado

Women's Economic Empowerment in Selected MENA Countries: The Impact of Legal Frameworks in Algeria, Egypt, Jordan, Libya, Morocco and Tunisia - OECD (OECD, 2017)
OECD's dissemination platform for all published content - books, serials and statistics
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (Chr. Michelsen Institute, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

The costs of corruption to the Mozambican economy. Why it is important to fight corruption in a climate of fiscal fragility - CIP and CMI (Centro de Integridade Pública (CIP) and Chr. Michelsen Institute, 2016)
What is the price that Mozambique has to pay for the widespread corruption in the country? What is the cost of corruption for the...
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Pobreza e Bem-Estar em Moçambique: Quarta Availação Nacional - Inquérito Ao Orçamento Familiar - Iof 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Pobreza e Bem-estar em Moçambique: Resumo da Quarta Availação Nacional - Inquérito ao Orçamento Familiar - IOF 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Mozambique: Report 8/2016 Country Evaluation Brief - Tvedten, Inge; Orre, Aslak (Norwegian Agency for Development Cooperation (Norad), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Government Decentralization Program in Indonesia - Nasution, Anwar (Asian Development Bank Institute, 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Accepted: 2016-08-26T11:02:32Z
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Rethinking Indonesia’s Informal Sector - Rothenberg, Alexander D.; Gaduh, Arya; Burger, Nicholas E.; Chazali, Charina; Tjandraningsih, Indrasari; Radikun, Rini; Sutera, Cole; Weilant, Sarah (World Development, 2016)
This paper reviews competing theories about the causes of informality in developing countries and uses new data to determine which theory best explains the persistence and scale of Indonesia’s informal sector. Using nationally representative survey data on micro, small, and medium-sized firms, we find that most of Indonesia’s informal firms are very small, micro firms, with less than five employees. These firms pay low wages, are relatively unproductive when compared to large firms, are managed by individuals with low educational attainment, predominantly supply products to local markets, and have not recently attempted to expand their operations. From a small-scale, qualitative survey of firms, we find that many informal firms do not register their businesses either because they have no desire to expand or borrow from formal financial sources, or because they are avoiding taxes. Finally, we evaluate the impact of Indonesia’s one-stop-shops for business registration program, a large-scale program that attempted to reduce registration costs. We find both that the program had no effects on firms’ informality rates, and we also find that it did not reduce the probability that workers were informally employed. Taken together, the evidence suggests that a combination of the rational exit and the dual economy theories best explains why so many firms in Indonesia are informal.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

JICA in Mozambique Brochure - Japan International Cooperation Agency (JICA) (2016)
1. What is JICA? Since joining the Colombo plan in 1954, Japan has been providing financial and technical assistance to developing countries through ODA (Official Development Assistance). JICA is the "one stop shop of Japan's bilateral ODA'', providing Technical Cooperation, ODA Loans (Concessional Loans) and Grant Aid. JICA has a network of more than 90 overseas offices. In Mozambique, JICA opened office in 2003. 3. Priority Areas in Mozambique: 1) Activation of Regional and Local Economies 2) Environment and Climate Change Action 3) Human Development & Capacity Building
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Imagining Agricultural Development in South–South Cooperation: The Contestation and Transformation of ProSAVANA - Shankland, Alex; Gonçalves, Euclides (World Development, 2016)
This paper discusses South–South cooperation by examining ProSAVANA, a flagship agricultural development program seeking to apply Brazilian experience to Mozambique. ProSAVANA is a joint Japan–Brazil–Mozambique initiative in the savannah zone of Mozambique’s Nacala Corridor region that was initially inspired by the Japan–Brazil PRODECER program in Brazil’s Cerrado region. ProSAVANA subsequently became the focus of fears about land-grabbing in the Nacala Corridor, attracting strong civil society contestation. We show how distinct imaginaries of agricultural development in Mozambique and Brazil were used to mobilize for and against ProSAVANA, thus revealing the contentious nature of the similarity claims underpinning South–South cooperation. In particular, we focus on the role of landscape imaginaries associated with the savannah and the Cerrado. We examine the use in the promotion and contestation of ProSAVANA of visual representations that draw on these imaginaries, including GIS maps of Mozambique’s savannah region made by Brazilian agribusiness consultants and an advocacy video of Brazil’s Cerrado region filmed by Mozambican land rights activists. Noting that the latest ProSAVANA planning documents differ significantly from those expressing its initial vision, we argue that the contestation of ProSAVANA has had a series of productive effects even before the program has moved to full implementation. These productive effects are visible not only in the program itself but also in the wider context of state-society relations shaping debates on South–South cooperation in Mozambique, Brazil, and beyond.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; M - ethnography / etnografia; Northern PEA; agriculture / agricultura; south-south cooperation / cooperação sul-sul

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Body.: Illness, Memory, and the Dynamics of Healing - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
When residents of Chimoio and Honde talk of the forceful and potentially perilous dimensions of spirits, healing, and illness, they frequently relate them to tchianhu wo atewe. Spirits, which embody various potencies and capacities, are integral to diurnal and nocturnal lives in urban and rural contexts alike. As shown previously, a wide range of spirits exhibit dynamics of re-/deterritorialization. Further, people relate to ancestral spirits, so-called vadzimu, in annual private rituals to secure the well-being of their dzindza and household, or they participate in more elaborate communal rituals led by authorities like the tchirenge, who invoke the ancestors’ protection from
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Conclusion.: Uncapturability, Dynamics, and Power - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Ethnography harbors the power of critique—political, social, and theoretical. Ultimately a capacity to destabilize, this orientation also applies when writing an account of the violence inherent to processes of state formation in Mozambique. While such critical potential may be realized in a number of ways, here I have privileged perspectives forged on the margins of the centers of power, supplemented by historical sources. But there is more to it than this: by privileging a decentering of institution-based notions of the state informed by multiple readings of Deleuze, a wholly different picture of what a state is—and might be
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Economy.: Substance, Production, and Accumulation - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
In After Kinship (2004), Janet Carsten employs “substance” to delineate important dimensions of classical understandings of kinship and personhood. She does so by reinterpreting Schneider’s (1980) studies on American kinship and revisiting Marilyn Strathern’s (1988) analyses of Trobriand kinship and in/dividuality. Based on these reinterpretations and, more generally, extensive comparisons between Indian, Melanesian, British, and American cases, Carsten specifically recontextualizes and questions the components of kinship as code and substance as argued by Schneider. Concentrating on substance, she argues that the term has a range of different connotations but is used in diverse ways, ranging from the stuff of relations
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Law.: Political Authority and Multiple Sovereignties - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Since the General Peace Agreement was signed in 1992 the legal, administrative, and political sectors of Mozambique have undergone multiple reforms that have exposed the complexity of its historical trajectories of law, violence, and authority. From the perspective of those living in the impoverished and frequently dangerous and violent urban and peri-ur-ban bairros, a great variety of agencies and authorities can be approached at times of difficulty or trouble. These range from n’angas, profetes, and police agents to government bureaucrats and Frelimo secretaries. This chapter explores the general situation in the marginalized communities making up the rural-urban continuum of Chimoio
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Sovereignty.: The Mozambican President and the Ordering of Sorcery - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Why does the Mozambican state attempt to control uroi —a force that is seemingly incompatible with the state rationale of both the postindependence Afro-Marxist era as well as the post–civil war period of neoliberal democracy? This chapter will broach this question through untangling the problematic relations between spirit and state within the context of AMETRAMO (Associação da Medicina Tradicional de Moçambique —the Association for Traditional Medicine in Mozambique), a state-sanctioned institution organizing so-called traditional healers. I will argue that the case of AMETRAMO exemplifies a statal mechanism for capture and control of the force fields and potencies of the
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Spirit.: Chiefly Authority, Soil, and Medium - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
This vision of sovereign power hovering above the relations between natural and human elements is relevant beyond genealogical analyses of biopower, pastoral power, and govenmentality. If we go beyond Foucault’s near exclusive context and subject of enquiry, Europe, these relations move to the forefront of social and political life. In Honde, crucial interconnections between polities of chiefly rule and traditional authority, cosmologies of land and the well-being of its inhabitants, and soil are present in a number of contexts. We have seen indications of this previously through Renamo’s appropriation of the traditional field, in Ngungunyane’s problematic relations with rainmaking capacities,
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Territory.: Spatio-Historical Approaches to State Formation - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
What does the notion of territory entail for state formation? As Elden (2013) has made clear in his recent genealogy of territory, it may be seen as a spatial extension of state power. While Elden’s point is crucial, in this chapter I will entertain the idea that the colonial state form is not different in its key dynamics from later state forms, as well as certain African polities, and in this way the chapter challenges the idea of the colonial state as radically different from earlier or later state forms. While basing myself on information from Manica Province, the empirical
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Violence.: War, State, and Anthropology in Mozambique - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
How is one to make sense of state formation as a predominantly violent process? More concretely, how is one, as an anthropologist, to understand one’s interlocutors’ repeated insistence on life being a sustained period of suffering ( sofrimento )? One point at which to start is with the most recent large-scale period of violence, namely the Mozambican civil war (1976–92). During this phase of violent upheaval, the traditional field was implicated in complex ways and its reality as a domain of the potential was actualized in various manners vis-à-vis state dynamics and war machine dynamics. By describing the civil war as
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Estrutura Geológica de Moçambique - Nogar Boca (2016)
Tema: Estrutura Geológica de Moçambique A estrutura geológica de Moçambique é resultado da interacção de vários processos, sobretudo os endógenos (internos) e exógenos (externos), que se fizeram sentir e ainda sentem-se na actual região da África Austral, onde Moçambique faz parte. Do ponto de vista geológico, Moçambique apresenta duas grandes unidades geológicas: Pré-câmbrico Fanerozóico
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; natural resources / recursos naturais

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

O papel da educação para a igualdade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 2005-2015 - Lucas, Geraldo Cebola João (Revista Litteris, 2015)
Este artigo tem como objecto “o contributo da educação para a equidade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 1997-2015”. O terceiro objectivo do milénio defende que para que possa alcançar o desenvolvimento sustentável nos países em vias de desenvolvimento e mesmo os já industrializados é preciso que a questão de género seja tomada como primordial nas políticas e estratégias de desenvolvimento. E tal pressuposto requer, como se defende nos objectivos, uma equidade de género e seu paralelo empoderamento. Porque acredita-se que a questão de género é transversal. É preocupação nesta pesquisa verificar se as políticas de género em Moçambique estão em consonância com o terceiro objectivo do milénio. Em segundo lugar, verificar o grau do cumprimento do terceiro objectivo do Milénio na cidade de Lichinga. A pesquisa é norteada pela seguinte pergunta de pesquisa: “ em que medida as políticas da educação moçambicana têm contribuído para a equidade e empoderamento do género no quadro do terceiro objectivo do milénio?”.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - portuguese / português; education / educação; empowerment / empoderamento; gender / género; youth / juventude

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Number: 2
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

PEDEC-NACALA Final Study Report Analysis Report: Strategic Master Plan on Strengthening of Nacala Corridor Region-Wide Freight Network for Agricultural and Mining Sectors - Oriental Consultants Global Co., Ltd.; RECS International Inc.; International Development Center of Japan Kokusai Kogyo Co., Ltd. (Japan International Cooperation Agency (JICA), 2015)
This document was prepared as an analysis report for sharing a study result on a particular theme as part of ‘The Project for Nacala Corridor Economic Development Strategies (PEDEC-Nacala)’ which is a technical assistance project supported by Japan International Cooperation Agency (JICA) for the Government of Mozambique. PEDEC-Nacala formulated integrated development strategies for corridor development by an integrated approach involving several sectors and also by giving consideration to environmental and social aspects. The actual strategies formulated in PEDEC-Nacala and details of the present situation of the Nacala Corridor Region are compiled into the PEDEC-Nacala Final Study Report
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura

Business licensing: a key to investment climate reform - Ing, Lili Yan; Magiera, Stephen; Widiana, Anika (Economic Research Institute for ASEAN and East Asia, 2015)
Reforming business licensing is a key starting point for improving the investment climate. Complex licensing procedures may encourage firms to remain unregistered, giving rise to difficulties later in accessing finance from formal financial institutions and constraining productivity and expansion. Across sectors, this can suppress the establishment of new firms and therefore the creation of new jobs, dragging down overall economic growth. Improving and reforming business licensing can significantly increase the number of businesses and thus help nurture employment creation. Several quick-win interventions are possible. First, there is a need to improve the quality of the business licensing website and help desk. The website and help desk should act as a frontline in dealing with investment regulations and policies for investors. Improvements should cover both hard and soft infrastructure of the website and help desk, including the skills of officials. Second, business license simplification should be continued by limiting licenses to those that serve their objective and cutting unnecessary licenses, and or consolidating licenses. Third, full implementation of electronic application and payment systems for business licenses should be fostered, together with increasing the nonfiscal incentives for firms to become registered. The registration system should also function as a nationwide database which could then be a source of reliable information both on firms and for firms, linked to government programs and grants, and business regulation updates. Fourth, a transparent system to show the progress of each business application should be set up, together with a recorded evaluation system in which users can provide feedback to improve the system. Finally, efforts in the medium term should focus on improving coordination among government agencies and clarifying the roles of central and local regulations, both horizontally and vertically.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

The land grabbers of the Nacala Corridor - UNAC (GRAIN, 2015)
A new report by Mozambique's National Farmers' Union (UNAC) and GRAIN shows there is a colonial-style scramble for Africa's farm lands under way. Politically-connected companies based in offshore tax havens have grabbed hundreds of thousands of hectares of farmland from peasants in Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; Important; L - english / inglês; Northern PEA; law / direito

Growth, capital accumulation and economic porosity in Mozambique: social losses, private gains - Castel-Branco, Carlos Nuno (Review of African Political Economy, 2015)
The Mozambican economy has been growing at an annual average of 7.5% for the best part of two decades, and has become one of the three most attractive economies for foreign direct investment (FDI) in sub-Saharan Africa. Yet, it has been ineffective and inefficient at reducing poverty and providing a broader social and economic basis for development. It is argued here that the dominant political economy of Mozambique is focused on three fundamental and interlinked processes, namely the maximisation of inflows of foreign capital - FDI or commercial loans - without political conditionality; the development of linkages between these capital inflows and the domestic process of accumulation and the formation of national capitalist classes; and the reproduction of a labour system in which the workforce is remunerated at below its social cost of subsistence and families have to bear the responsibility for maintaining (especially feeding) the wage-earning workers by complementing their wages or trying to maintain the availability of the enormous idle reserve of labour. This article focuses on economic porosity, which, arguably, is a dominant factor in promoting the linkages between domestic and foreign capital, nurtured, supported and mediated by the state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Revoltas da fome: protestos populares em Moçambique (2008-2012) - Brito, Luís de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Instituto de Estudos Sociais e Económicos, 2015)
Em Fevereiro de 2008 e Setembro de 2010, as cidades de Maputo e Matola foram palco de protestos violentos contra a subida do custo de vida, protagonizados por grupos de populares. Tais protestos foram logo depois replicados em algumas outras cidades do país, mas numa dimensão bem mais restrita e rapidamente controlados pelas forças policiais. Em Novembro de 2012, um novo protesto se desenhou, mas a acção repressiva imediata nos locais críticos de concentração dos populares pelas forças da polícia, que nos últimos anos tinha sido reforçada fortemente em homens e material, impediu que a violência se generalizasse, ainda que não tenha evitado a paralisia quase total da actividade no grande Maputo durante um dia e meio. Neste relatório procuramos mostrar que, se estas revoltas se enquadram num movimento mais amplo que desde 2008 tem abalado muitos países em consequência do aumento e da alta volatilidade dos preços alimentares no mercado internacional, elas exprimem sobretudo dinâmicas económicas locais e são um resultado da exclusão social e política a que são votadas as camadas sociais urbanas mais pobres em Moçambique. O relatório começa por apresentar uma breve perspectiva histórica e caracterização da natureza da economia moçambicana e da tradição política autoritária que tem sido dominante desde a proclamação da independência, ainda que coexistindo com uma profunda mudança nas alianças políticas do partido no poder, para depois abordar a questão alimentar e do custo de vida, assim como o contexto imediato dos protestos, os discursos e representações sobre os mesmos e o tipo de resposta por parte do governo.
978-989-8464-23-1
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

An Analysis of Mozambique’s Political and Economic Networks - Chivangue, Andes; Cortez, Edson (CEsA - research center part of CSG/Research in Social Sciences and Management, 2015)
This paper analyses the social networks existing among politicians and economists in contemporary Mozambique, using the SNA-Social Networks Analysis method to identify the links between these individuals, to discern their relationships and to measure both the density and the centrality of the political-business network. Mozambique’s political and business elite is thus identified. A network sociogram is presented identifying the individual position in the network and the linkages among these individuals and several positional metrics of the individuals in the network are estimated, allowing identifying each individual and its influence in the network. As this network is resource accumulation driven, this exercise permits to identify the main political and economic individual active in Mozambique economy. President Guebuza define the major network centre and other individuals, Joaquim Chissano, the former president, and Graça Machel, the widow of another former president. Policy implications are derived and the links between them displayed, allowing for an accurate view of Mozambique’s political and business world.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Os Municípios dos “Outros”. Alternância do poder local em Moçambique? O caso de Angoche - Rosário, Domingos Manuel do (Cadernos de Estudos Africanos, 2015)
As eleições municipais de 2003 marcaram o início do exercício do poder local pela Renamo no município de Angoche. Quais são os factores explicativos desta situação eleitoral local? A partir de uma perspectiva sócio-histórica, este artigo procura compreender como é que a evolução política e administrativa destes territórios influenciou a lógica do poder local. São as relações estabelecidas entre as populações e o Estado e a forma como a municipalização foi desenhada e implementada desde 1994 pela Frelimo que não proporcionam condições favoráveis à criação de um pluralismo político, na medida em que o partido dominante consegue, através do controlo que exerce sobre o Estado central, instrumentalizar os recursos e fortificar suas bases políticas e eleitorais.
Number: 30
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; L - portuguese / português; Northern PEA; electoral geography / geografia eleitoral

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Publisher: International Research Center for Energy and Economic Development (ICEED)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

The land grabbers of the Nacala Corridor: A new era of struggle against colonial plantations in Northern Mozambique - UNAC; GRAIN (UNAC and GRAIN, 2015)
This report looks at the companies already setting up agribusiness operations in the Nacala Corridor, an area that the government has prioritised for agribusiness development. These companies, typically structured through offshore tax havens and often connected to Mozambican political elites, have been grabbing lands and extracting wealth in ways reminiscent of the country's colonial days.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Hunger Revolts and Citizen Strikes: Popular Protests in Mozambique, 2008-2012 - Brito, Luis de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Institute of Development Studies/Instituto de Estudos Sociais e Economicos, 2014)
In February 2008 and September 2010, the cities of Maputo and Matola were the scene of violent protests against the rise in the cost of living, undertaken by groups of ordinary citizens. Immediately afterwards, these protests were replicated in some other Mozambican cities, but on a much smaller scale, and they were quickly brought under control by the police. In November 2012, a new protest was set in motion, but immediate repressive action by the police (which in recent years has been greatly strengthened in men and material) in the key places where people were gathering prevented the violence from spreading, although it did not prevent the near total paralysis of activity in greater Maputo for a day and a half.
Accepted: 2014-10-30T10:10:14Z Publisher: Institute of Development Studies
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

The geographic and sectoral patterns of large-scale farmland investments in sub-Saharan Africa - Schoneveld, George Christoffel (Food Policy, 2014)
Following the food and energy price crises of the mid 2000s, sub-Saharan Africa has become one of the largest recipients for large-scale farmland investments. While much has been written on the phenomenon, scant reliable empirical evidence is available as to the precise geographic and sectoral patterns and underlying drivers. Employing strict data quality requirements, this paper addresses these knowledge gaps by analyzing 563 farmland projects that have been established between 2005 and 2013 in sub-Saharan Africa. Findings show that the investment intensity and associated risks are not geographically uniform. Moreover, the study highlights a number of popular misconceptions regarding investor origin and their sectoral interests and motives.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Perfil Do Distrito De Macomia Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Macomia; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza

Mozambique rising: building a new tomorrow - Ross, Doris C. (International Monetary Fund, African Department, 2014)
This publication highlights Mozambique's remarkably strong growth over the two decades since the end of the civil war in 1992, as well as the major challenges that remain for the country to rise out of poverty and further its economic development. Chapters explore such topics as the role of megaprojects and their relationship to jobs and growth; infrastructure and public investment; Mozambique's quest for inclusive growth; developing the agricultural sector; and building a social protection floor
OCLC: ocn879526832
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; Social Protection PEA; agriculture / agricultura; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; infrastructure / infrastrutura; social protection / proteção social

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Number: 2
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

“What is a House without Food?”: Mozambique’s Coal Mining Boom and Resettlements (Human Rights Watch, 2013)
“What is a House without Food?” Mozambique’s Coal Mining Boom and Resettlements
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

A Rede de Negocios da Frelimo no Norte - , Erik (Verdade - A verdade a cada palavra, 2013)
O investimento em energias e infra-estruturas pode transformar o negligenciado norte e afectar a sucessão presidencial. Andarko e outras companhias petrolíferas prevêem que o gás descoberto em Cabo Delgado pode duplicar o produto interno bruto anual. Por enquanto acredita-se que as vastas reservas de carvão se encontram na província do Niassa. O centro de gravidade de oportunidades económicas de Moçambique parecem se transladar para o norte. O governo está a atrair investidores estrangeiros para ajudarem na transformação desses recursos naturais em rendimentos públicos para o que era até agora um dos países mais pobres do mundo.
Keywords: #Reporting & Media / Reportagem & Mídia; G - north / norte; GP - Cabo Delgado; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Accepted: 2017-12-05T13:07:47Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Translating the Idea of the eGovernment One-Stop-Shop in Indonesia - Wahid, Fathul (Information and Communication Technology, 2013)
This study aims to understand how the idea of an eGovernment one-stop-shop (OSS) has been translated into a new setting. Since the beginning of 2000, this idea has been implemented in a variety of ways by Indonesian local governments. Using an interpretive case study in the city of Yogyakarta, the study revealed that the specificity of each setting influences the translation process of the idea of OSS during its institutionalization. It also identified a set of editing rules used during the translation process. These include the editing rules concerning context (e.g., internal readiness); logic (e.g., corruption eradication); and formulation (e.g., standardized processes). The study also found that the idea translation was not a single round process.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Promoting SME development in Indonesia - Mourougane, Annabelle (OECD Economics Department Working Papers, 2012)
Micro, small and medium-sized firms (MSMEs) are a key source of employment and economic growth in Indonesia. They contributed to the country’s economic resilience during the 2008-09 financial crisis. But many suffer from low productivity, curbing their role in boosting living standards. There are several ways to spur MSME productivity growth over the medium term. The first route would be to encourage the formalisation of small firms. Lessening red tape through simplification of the licensing process and lower tax compliance costs would help. Avoiding excessive rises in the minimum wage in provinces where it is already at a reasonable level would also be important. Looking forward, it would be useful to remove rigidities in the formal labour markets, while moving to some form of unemployment benefit system to insure workers against job-loss risks. The second route would be to boost investment. Clarifying property rights for real estate, and making the information collected by the credit bureau available to all financial institutions would ease access to finance. At the same time, the development of financing alternatives such as venture capital, leasing or micro-finance would enhance credit supply. The poor state of infrastructure, in particular in the transportation and electricity sectors, is also perceived as an important impediment to investment and could be remedied by increasing public infrastructure spending on cost-effective projects. The third route would be to enhance the quality of human resources. The country suffers from a lack of skilled workers, and policies should aim both at increasing the pool of workers and making education and training institutions more responsive to evolving labour-market demand. Indonesia has a long tradition of supporting MSMEs. But responsibilities between the different levels of government and within the central government need to be clarified to minimise overlap and inefficiencies. A rigorous assessment of existing programmes would allow schemes to be consolidated and scarce public funds to be directed to their most cost-effective uses.
Number: 995 Publisher: OECD
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

The Human Rights Impacts of Tree Plantations in Niassa Province, Mozambique - Seufert, Philip; Santos, Ricardo (FIAN International, 2012)
This study investigates the impairing of the rights of peasant communities through the establishment of tree plantations in Niassa province, Mozambique. More particularly, it looks at the impacts of the operations of Chikweti Forests of Niassa on the local population in the districts of Lago, Lichinga and Sanga. In order to do so, it presents an introductory chapter on the general context of Mozambique and the legal framework. This legal framework will serve as a basis on the analysis of the findings of this study using a human rights approach. It contains an overview of national and international provisions relevant to the case. This includes Mozambican national legislation and policies, as well as standards under international human rights law. Regarding the latter, it puts a particular focus on extraterritorial obligations (ETOs), recently clarified by the Maastricht Principles on Extraterritorial Obligations, and includes provisions related to access to land and related resources, as contained in the Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; rural development / desenvolvimento rural

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

The White Gold: The Role of Government and State in Rehabilitating the Sugar Industry in Mozambique - Buur, Lars; Mondlane Tembe, Carlota; Baloi, Obede (The Journal of Development Studies, 2012)
This article examines the rehabilitation of the sugar industry in Mozambique after the General Peace Accord in 1992, engaging primarily and critically with certain aspects of the business-state literature. It explains why the sugar sector was rehabilitated from the perspectives of Mozambican state, government and industry actors. The article argues that support for the industry cannot be identified in singular and one-dimensional terms, but must include a variety of attributes of support that emerged from a post-independence fusion of industry, state and government officials' historical experiences of success and failure in the industry, and pragmatic as well as longer-term ideological stances. This, it is argued, created a ‘mediating bureaucracy’ that could broker between the diverse interests and aspirations of state/government and industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/00220388.2011.635200
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Gender Disparity in Laws and Female Employment - Amin, Mohammad (Mimeograph, 2012)
Berkeley Electronic Press Selected Works, In a large sample of firms in 66 developing countries, it is shown that gender specific disparity in the laws favoring males over females tends to lower the employment of females relative to males at the firm level. However, this relationship between gender disparity in laws and employment is driven by small and medium firms, and it does not hold for the sample of large firms. However, the relationship holds equally in rich vs. poor countries, small vs. large cities within countries and among firms with and without female owners. We also confirm a sharp negative effect of gender disparity in the laws on the absolute level of employment of females. In short, in the presence of gender disparity in the laws, suitable reforms or policy measures promoting female employment may be required to achieve greater employment of women and greater gender parity in employment.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

From Negligence to Populism: An Analysis of Mozambique’s Agricultural Political Economy - Rosário, Domingos Manuel do (2012)
The paper analyses the changing configuration of the political system since the Rome Peace Agreement of 1992. It discusses how the “political settlement” underlying the Peace Agreement and the outcomes of multiparty elections thereafter have shaped governance, including policy-making concerning the agriculture sector and the rural economy. The paper argues that private interests and electoral objectives have been important drivers of policy decisions taken by the governing elites concerning the agriculture sector and local governance, with precedence over donor influence. By contrasting the political choices and governance approaches adopted by the two different presidential administrations in office since the first multiparty elections were held in 1994, it is argued that one (led by Joaquim Chissano) is marked by features of “neopatrimonialism”, whereas the other (led by Armando Guebuza) is showing signs of electoral “populism”. The former is characterised by significant rent distribution by the governing elite to a narrow “selectorate”. The latter is manifested by a paternalistic and politically mobilising discourse emanating directly from the President and appealing to the broader electorate, particularly the rural population of the central and Northern region of the country, who has been traditionally opposed to the ruling party
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

How do female entrepreneurs perform? Evidence from three developing regions - Bardasi, Elena; Sabarwal, Shwetlena; Terrell, Katherine (Small Business Economics, 2011)
Using the World Bank Enterprise Survey data, we analyze performance gaps between male- and female-owned companies in three regions—Eastern Europe and Central Asia (ECA), Latin America (LA), and Sub-Saharan Africa (SSA). Among our findings are significant gender gaps between male- and female-owned companies in terms of firm size, but much smaller gaps in terms of firm efficiency and growth (except in LA). Part of the reason women run smaller firms is that they tend to concentrate in sectors in which firms are smaller and less efficient (in ECA and SSA). By contrast, we find no evidence of gender discrimination in access to formal finance in any of the three regions, although in ECA women are less likely than men to seek formal finance. Finally, while female entrepreneurs receive smaller loans than their male counterparts, the returns from each dollar they receive is no lower in terms of overall sales revenue.
Number: 4
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender and the Business Environment for New Firm Creation - Klapper, Leora F.; Parker, Simon C. (The World Bank Research Observer, 2011)
Abstract. The authors summarize the extant literature on the relationship between gender and entrepreneurship. They note significant quantitative gender differ
Number: 2 Publisher: Oxford Academic
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

The Preparatory Survey on Nacala Port Development Project in the Republic of Mozambique Final Report - JICA (Japan International Cooperation Agency (JICA), 2011)
Japan International Cooperation Agency (JICA) decided to conduct the preparatory survey on Nacala Port Development Project in the Republic of Mozambique, and organized a survey team headed by Dr. Kobune of Ides and consists of OCDI, Oriental Consultants, ECOH CORPORATION, and Ides between June, 2010 and April, 2011. The survey team held a series of discussions with the officials concerned of the Government of the Republic of Mozambique, and conducted field investigations. As a result of further studies in Japan, the present report was finalized. I hope that this report will contribute to the promotion of the project and to the enhancement of friendly relations between our two countries. The Study Team compiled this report, which proposed the Medium and Long-term Development Plan of Nacala Port with the target year of 2030 and the Short-term Development Plan, and selected the Urgent Rehabilitation Project through close consultations with officials of the Mozambique Government, in particular, Ministry of Transport and Communications (MTC), Portos e Caminhos de Ferro de Mocambique E.P. (CFM), as well as the Management of Corredor de Desenvolvimento do Norte (CDN), and authorities concerned.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Ten years of single window implementation: lessons learned for the future - Koh, Jonathan (Global Trade Facilitation Conference 2011, 2011)
This paper examines the Single Window concept and its developments in practice over the last 10 years and provides an analysis of its development over time. An overview of the emerging information technology that would impact its future development is also presented. The paper also examines regional trends in Single Window implementation, based on a survey of tenders documents issued by various countries in the recent years. Finally, it offers an outlook on its future development and provides a number of recommendations.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Decentralization and Economic Performance in Indonesia - Pepinsky, Thomas B.; Wihardja, Maria M. (Journal of East Asian Studies, 2011)
Indonesia's 1999 decentralization law gave local governments in Indonesia an unprecedented opportunity to adopt prodevelopment policies. In this article, we study whether decentralization has in fact generated improved economic performance in Indonesia. Using a synthetic case control methodology, we argue that Indonesian decentralization has had no discernable effect on the country's national-level economic performance. To explain why not, we use subnational data to probe two political economy mechanisms-interjurisdictional competition and democratic accountability-that underlie all theories linking decentralization to better economic outcomes. Our findings suggest that extreme heterogeneity in endowments, factor immobility, and the endogenous deterioration of local governance institutions can each undermine the supposed development-enhancing promises of decentralized government in emerging economies such as Indonesia.
Number: 3
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Local economic governance: a survey of business operators in 245 districts/municipalities in Indonesia, 2011 - The Asia Foundation; Regional Autonomy Watch (The Asia Foundation, 2011)
Decentralization has been underway in Indonesia for more than ten years, but recently many have challenged the how effectively decentralization – and even democratization – is being implemented. Deterioration in the quality of public services, the many corruption cases involving local governments, and low economic growth rates in some regions have prompted discourse about whether the country is making a reversal away from decentralization and democratization. We recognize that the move toward regional autonomy has not been without its faults. Nevertheless, a choice was made to strengthen democracy and move towards local autonomy based on the problems created by the centralistic, authoritarian system of the previous regime. Yet it is unfair to judge regional autonomy a failure after it has been implemented for such a short time, and under a somewhat inconsistent policy framework. Since 2001, the Regional Autonomy Watch (KPPOD) and The Asia Foundation have aimed to present a clear picture of the quality of regional economic governance from the perspective of business owners. Our studies provide input to government at the central, provincial and regional/municipal levels, as well as information to other stakeholders regarding efforts that can be undertaken to promote improve economic growth under regional autonomy. This year’s study finds significant variation among regions in the quality of economic governance. This indicates that despite many limitations, some regions have used the opportunities provided by autonomy to foster good governance while others have not. It is hoped that this present study, and the awards presented to regencies and municipalities with the best performance, will promote a healthy competition among regional leaders. It is also envisioned that local governments whose performance is still low can learn from their neighbors who are doing better, and be inspired to improve. We recognize that improving economic governance requires a strong commitment and hard work, not only from the heads of regions but from all ranks of government officials, politicians, business owners and other stakeholders. This study can help set priorities for reform of local economic governance, identifying areas for immediate improvement that are relatively easy to achieve but have the potential of significant impact. Other aspects may need more time for improvement.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; M - survey / inquérito; Northern PEA; decentralization / descentralização

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Final Report 1 of 3 Summary - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part I-II - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-IV - JICA (Japan International Cooperation Agency (JICA), 2010)
The Study Road (N13: Cuamba – Mandimba – Lichinga), as part of the two Mozambican corridors (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors), provides a strategic link to the Malawi Border at Mandimba with the ports of Nacala and Pemba, in Nampula and Cabo Delgado Provinces respectively. Although the Study Road has much potential for stimulating development and reducing poverty throughout the entire northern area of Mozambique by enabling efficient connection, the section concerned is the only unpaved section. The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-V - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors)
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part VI: Environmental and Social Considerations - JICA (Japan International Cooperation Agency (JICA), 2010)
In response to the request from the Government of the Republic of Mozambique, the Government of Japan decided to conduct the Preparatory Survey on Road Improvement Plan in Nacala Development Corridor (N13: Cuamba-Mandimba-Lichinga) and entrusted the study to the Japan International Cooperation Agency (JICA). Objectives of the study: (1) The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. (2) Formulation and recommendation of the “Regional Development Program” intended for Niassa Province is also the objective of the Study.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part IV Economic Feasibility Study - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter1 Existing Traffic Flow Patterns This chapter aims to analyze traffic flow patterns on the Study Road based on various information in order to conduct the appropriate traffic demand forecast. Chapter 2 International Goods Transportation Though Nacala Corridor This chapter aims to discuss the current condition of international goods transportation through Nacala Corridor in order to estimate future traffic demand on the Study Road. Chapter 3 Traffic Demand Forecast 3.1 Macro-Economic Background 3.2 Forecasting Methods 3.3 Traffic Demand Forecast 3.4 Results of Traffic Forecast Chapter 4 Economic and Financial Analysis (Cuamba-Mandimba Section) The Study objective is “to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing earth/ gravel roads in the rural areas to paved roads.” For the purpose of the economic evaluation, it is important to first define the existing state of the Project road for the base case, and then to define the alternatives to be analyzed, and finally the structure of the analysis.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part V Cross-Border Facilities - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter 1 Mozambique-Malawi Border Control and Facilities 1.1 Current Condition of Cross-Border Traffic between Mozambique and Malawi 1.2 Border Facilities between Mozambique and Malawi 1.3 Border Control System and Border Facilities Chapter 2 Mandimba Border Control and Facilities 2.1 Characteristics of Mandimba Border Area 2.2 Cross-Border Traffic and Cargo 2.3 Mandimba Border Post and Facilities 2.4 Chiponde Border Post and Facilities Chapter 3 Strategy for Upgrading Border Control and Facilities 3.1 SADC-COMESA Regional Strategy 3.2 One Stop Border Posts 3.3 Mozambique-Malawi Bilateral Strategy Chapter 4 Implementation Approach for Upgrading Mandimba Border Facilities 4.1 Needs Assessment and Proposed Approach for Implementation 4.2 Methodology for OSBP Phased Introduction 4.3 Challenges to OSBP Introduction Chapter 5 Border Development Strategy for Upgrading Mandimba Border Facilities 5.1 Traffic Demand Forecast at Mandimba-Chiponde Border 5.2 Proposed Implementation Policy 5.3 Proposed Facility Planning for Phased Introduction of OSBP
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Economia extractiva e desafios de industrialização em Moçambique - Castel-Branco, Carlos Nuno (Instituto de Estudos Sociais e Económicos (IESE), 2010)
A experiência económica de Moçambique é frequentemente apresentada como um exemplo de sucesso na promoção de rápido crescimento com estabilização e redução da pobreza. Paradoxalmente, a economia nacional mantém anormalmente elevadas taxas de dependência em relação a fluxos externos de capitais, tanto oficiais (ajuda externa) como privados (investimento directo estrangeiro e empréstimos no sistema bancário internacional). Como é que este nível de dependência é consistente com a história de sucesso? Se o investimento privado é tão dependente de fluxos externos de capitais, e se estes fluxos reflectem sobretudo os interesses globais dos grandes investidores multinacionais interessados em explorar os recursos naturais (terra, florestas, minerais e energéticos) de Moçambique, que padrão de produção e comércio está sendo criado? Não será, a continuação desta dependência profunda, um indicador da fragilidade estrutural da base produtiva, comercial e fiscal da economia? Ao longo da última década e meia, a eficácia do crescimento da economia em reduzir pobreza, medida pela elasticidade da redução da percentagem da população que vive abaixo da linha da pobreza em relação à taxa de crescimento do Produto Interno Bruto (PIB), tem vindo a reduzir. Até que ponto é que a redução da eficácia do crescimento económico a reduzir pobreza reflecte os padrões de acumulação, crescimento e distribuição gerados pela dependência da economia em relação ao investimento privado estrangeiro (concentrado em grandes projectos de recursos naturais)? Até que ponto seria esta eficácia ainda pior na ausência de ajuda externa para financiar o investimento público? Este artigo concentra-se da discussão das causas estruturais das fraquezas dos padrões de acumulação económica em Moçambique. O artigo desenvolve o conceito de economia extractiva e relaciona-o com a história e a economia política do padrão de acumulação, distribuição e reprodução. Esta discussão é realizada revisitando as análises históricas e os dados oficiais da economia moçambicana e, nesse processo, explorando duas vertentes relacionadas: a composição do crescimento económico e o seu impacto na estabilidade estrutural da macroeconomia de Moçambique. Finalmente, o artigo discute alguns desafios fundamentais para a transformação destes padrões e, por conseguinte, para o processo de industrialização.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Small and Medium Enterprises (smes) Access to Finance in Selected East Asian Economies - Harvie, Charles; Oum, Sothea; Narjoko, Dionisius A (ERIA - Economic Research Institute for ASEAN and East Asia, 2010)
Findings from ERIA’s SME research project in FY 2009 confirms that access to finance is amongst the most critical factors determining the competitive readiness of regional SMEs and their ability to fully exploit and participate in the global economy and business opportunities from regional economic integration and, in particular, participation in regional production networks. Well recognized in the literature, access to funding is the lifeblood of any enterprise, enabling it to grow, and to generate more output and employment. There is considerable evidence to support the contention that SMEs, in particular, face a number of obstacles and problems in accessing finance, mainly related to their limited resources and perceived risk by lenders. This is particularly problematic and worrisome for policy makers, given that SMEs and entrepreneurship are widely recognized as being the key sources of dynamism, innovation, and flexibility in advanced industrialized, emerging market and developing economies, and are major net job creators in these economies. Without access to finance, SMEs are unable to invest, impairing their capacity to: improve productivity; raise competitiveness; promote innovation; generate employment; and contribute to economic growth and development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; ⛔ No DOI found

The Expansion of Tree Monocultures in Mozambique. Impacts on Local Peasant Communities in the Province of Niassa - Overbeek, Winfridus (Movimento Mundial pelas Florestas Tropicais, 2010)
This publication is the result of a visit to Mozambique in November 2009 by two activists involved in the struggle against tree monocultures in the Brazilian state of Espírito Santo. This visit was made possible by the World Rainforest Movement (WRM) with the goal of exchanging experiences about large-scale tree monocultures. With more than 40 years of dealing with monoculture plantations and expansion, Brazil has a lot of experience in this area. At the same time, affected communities and supporting organizations in the country have led several struggles and acts of resistance and formed alliances, which nearly ten years ago resulted in the foundation of the Alert against the Green Desert Network (Rede Alerta contra o Deserto Verde). In the past few years, WRM has been made aware of the fact that more and more tree monocultures are being planted in Mozambique. Since Brazil and Mozambique have in common Portuguese as their official language, the idea arose to promote the exchange between the two countries so as to: − exchange experiences with the affected communities about the impacts; − better understand the current situation of the introduction and expansion of tree monocultures in Mozambique; and, − identify organizations involved or interested in the subject. This visit would not have been possible without the invaluable help of our friends at UNAC (União Nacional de Camponeses - National Peasant Union) in Mozambique, and UCA (União dos Camponeses e Associações de Lichinga - Union of Peasant and Associations of Lichinga), who volunteered to receive and accompany the Brazilian delegation and organized the visits to the communities. We also want to thank Via Campesina Brasil for their support in this initiative.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural

Gender and poverty in Mozambique - Tvedten, Inge (CMI, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

Género e pobreza em Moçambique - Tvedten, Inge (CMI, 2010)
A igualdade de género e o empoderamento das mulheres estão no centro das agendas do governo e dos doadores na África Sub-Sahariana, mas no geral não conseguiram ter impacto. Mais do que a ‘integração’ do género, é necessária mais atenção às variações da posição das mulheres. Numa série de três estudos sobre políticas de género e feminização da pobreza em Moçambique, foram encontradas diferenças significativas entre o norte e o sul, bem como entre as áreas rural e urbana. É essencial que se compreendam estas variações para se desenhar políticas e intervenções relevantes para a melhoria das condições das mulheres no país.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; empowerment / empoderamento; gender / género; poverty / pobreza

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Relatório para o Governo da Província de Cabo Delgado e Agência Espanhola de Cooperação Internacional para o Desenvolvimento (AECID) - Umarji, Mariam; Makda, Sadya; Paulo, Arsénio; Lalá, Aly (SAL & Caldeira, 2009)
O relatório que se segue retrata a avaliação conduzida ao Sistema de Gestão de Finanças Públicas da Província de Cabo Delgado considerando o ciclo orçamental do ano de 2008, considerando a informação de contabilidade, reporte e auditoria relacionada com este ano mas produzida em 2007 e em 2009. A avaliação teve como base a Metodologia PEFA – Despesa Pública e Responsabilidade Financeira – devidamente adaptada ao nível subnacional (província) de acordo com as orientações metodológicas emanadas pelo Secretariado PEFA. Foram utilizados um total de 25 indicadores para a avaliação. Os indicadores reflectem a situação actual do sistema e fornecem um ponto de comparação para avaliações ou seguimentos futuros dos progressos esperados nos processos de planificação, orçamentação, contabilidade, reporte e auditoria da província. Esta Avaliação Sumária apresenta as constatações finais da equipa de consultores sendo fruto do trabalho de campo realizado para inquérito e recolha de evidência combinada com a revisão documental de informação recebida e disponibilizada de forma a se poder realizar a avaliação dos diferentes indicadores.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; budget / orçamento; fiscal policy / política fiscal

Relatório Final da Pesquisa sobre o Impacto da Descentralização dos Fundos Sectoriais de Estradas, Águas e de Construção Acelerada de Salas de Aulas nas Províncias, nos Distritos e nas Autarquias Locais - Kulipossa, Fidelx Pius; Nguenha, Eduardo Jossias (The Open University consultancy, 2009)
A 17a Sessão Ordinária do Conselho de Ministros realizada em 2007 tomou a corajosa decisão de descentralizar os fundos dos sectores de estradas, águas, agricultura, e infra-estruturas de educação e saúde para garantir a implementação efectiva da Lei 8/2003 sobre os Órgãos Locais do Estado e materializar os objectivos estratégicos definidos no PARPA II e no Plano Quinquenal do Governo. Tal decisão, em parte, reconhece que a pobreza absoluta que flagela muitos cidadãos está estreitamente ligada à falta de acesso aos serviços básicos tais estradas, água potável, infra-estruturas escolares e de saúde e outros serviços úteis para a sobrevivência e sustentabilidade da vida humana. Com efeito, presumia-se que ao se descentralizar estes fundos sectoriais para os níveis provinciais e distritais, as instituições locais teriam maior capacidade de resposta às demandas da população em termos de prestação de melhores serviços, de maneira que ela estivesse mais satisfeita e participasse activamente na vida política e económica do país. Em termos de produção legislativa, regista-se avanço significativo na descentralização de fundos sectoriais. Porém, sendo essa legislação muito recente e em fase primária de sua implementação, constatam-se algumas reservas na implementação efectiva da mesma. Por exemplo, os progressos sectoriais na descentralização de fundos são diferenciados. No sector de estradas, os fundos são geridas e os pagamentos efectuados a partir do nível central através da Administração Nacional de Estradas (ANE). Relativamente aos sectores de água e de educação (construção acelerada de salas de aulas) os fundos são geridos a nível provincial e os pagamentos feitos nos dois níveis: provincial e distrital. A leitura do processo, e com respeito às constatações feitas nas províncias de Nampula e Gaza, onde decorreu o trabalho de campo, revelou diferenças peculiares nos avanços e na forma de abordagem da descentralização nas duas províncias, particularmente nos aspectos referentes a critérios de planificação, definição de prioridades, alocação de recursos e fluxos financeiros. As diferenças verificadas para as duas províncias, que podem ser explicadas, em parte, pela diferença de maturidade na condução dos processos de descentralização entre Nampula e Gaza, sendo a primeira mais experiente, não inibem concluir que, em termos gerais: (1) a descentralização de fundos sectoriais ainda não é efectiva; (2) o envolvimento das instituições de planificação e consulta comunitária é efectivo; (3) o sistema de prestação de contas é complexo, moroso e contraproducente; (4) o sistema de monitoria e avaliação ao nível distrital pode ainda ser melhorado; (5) a capacidade de manutenção ao nível distrital precisa de fortalecimento; (6) há fraco envolvimento do sector privado na prestação de alguns serviços; (7) há desarticulação institucional na aplicação de alguma legislação; (8) os critérios de atribuição de fundos sectoriais são inconsistentes e pouco divulgados; e (9) há, nos distritos, falta de uma perspectiva multisectorial e sistemática de planificação. Face aos problemas identificados, este Relatório Final propõe algumas recomendações: nova abordagem sobre os fundos sectoriais, particularmente a sua integração nos PESOD; alinhamento dos instrumentos de planificação estratégicos locais com os nacionais; regulação em legislação própria dos critérios de alocação de fundos, capacitação institucional entre outras acções.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; education / educação; infrastructure - roads / infrastructura - estradas

Muslims of northern Mozambique and the liberation movements - Bonate, Liazzat J. K. (Social Dynamics, 2009)
Despite the fact that the liberation war occurred in northern Mozambique, where a considerable number of Muslims lived, their contribution to the independence struggle has been little studied. This paper focusses on their participation in two nationalist liberation movements, Mozambican African National Union (MANU) and Frente de Libertação de Moçambique (FRELIMO), and demonstrates that the prevailing idea in scholarship about Muslims’ aloofness from the liberation struggle is unjustified. It argues that Muslim support and participation in the liberation movements stemmed primarily from grassroots African nationalism. Like most Africans, Muslims wished to end colonialism and recover their land from the Portuguese. African Muslims of northern Mozambique were well suited to support these movements, because Islam and chieftainship were linked to each other. Chiefs were believed to be the ‘owners’ and ‘stewards’ of the land, and a majority of Muslim leaders, whether traditional chiefs (régulos, in Portuguese) or Sufi leaders (tariqa khulafa’, in Arabic), were from the chiefly clans. Most importantly, Muslims of northern Mozambique had close historical and cultural ties to Tanganyika and Zanzibar, especially through Islamic and kinship networks. The involvement of Muslims in the liberation movements of those regions, in particular in Tanganyika African National Union (TANU), inspired and encouraged the Muslims of northern Mozambique to support MANU and FRELIMO, especially since these two movements were launched in Tanganyika and Zanzibar with TANU backing and the participation of Muslim immigrants from northern Mozambique.
Publisher: Routledge _eprint: https://doi.org/10.1080/02533950903076378
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
ISBN 978-91-85735-17-4
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Publisher: Labour, Capital & Society
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found

The politics of gradualismo: popular participation and decentralised governance in Mozambique - Buur, Lars (Rethinking Popular Representation., 2009)
The question of how to proceed with democratic decentralisation has been of political concern in Mozambique over the past decade. In accordance with post-war constitutional commitments to démocratisation after the country’s post-independence flirtation with socialism and a high degree of centralism, the process of decentralisation has taken two forms. First, a system of locally elected governments in the form of municipalities (municipios) for the urban and semi-urban areas was approved in 1997 to cover the devolution of direct although limited powers and functions to autonomous elected bodies. The Municipal Law (2/1997) made provision for locally elected municipalities (autarquias locais) in 33 urban or peri-urban settings.1 Second, for the rest of the population (roughly .70 percent) and the local state administration, the process of decentralisation has taken the general form of de-concentration and a transfer of responsibility to lower level bodies within the state sector combined with different forms of participatory mechanisms for representation and consultation. These participatory mechanisms are grounded in community- based organisations claiming representative status on the basis of identity, interest, community, and similar factors.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; governance / governação

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Publisher: Falmer : University of Sussex
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

Higher fuel and food prices: impacts and responses for Mozambique - Arndt, Channing; Maximiano, Nelson; Thurlow, James T.; Nucifora, Antonio M. D. (Agricultural Economics, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer-term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (World Bank, 2008)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people— sectors that are more export oriented, labor intensive, and knowledge driven. These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past. This report is different. Its objective is to provide a better understanding of barriers to investment and doing business that may be common to all investors and those that affect women entrepreneurs disproportionately. The report examines newly available data from more than 4,800 surveyed firms in the formal sector in eight Middle East and North African countries (the Arab Republic of Egypt, Jordan, Lebanon, Morocco, Saudi Arabia, the Syrian Arab Republic, Gaza and the West Bank, and the Republic of Yemen). These surveys detail firm characteristics and the responses of male- and female- owned firms to questions about perceived barriers along 18 categories of the investment climate. The purpose of the report is threefold: • to provide an overview of the characteristics of female- owned firms in the region; • to analyze gender- specific barriers that exist across the region or within countries; and • to identify other factors outside the business environment that might affect women’s entrepreneurship. The report finishes with policy recommendations on how to reduce the identified barriers and create a level playing field for women entrepreneurs. The report acknowledges limitations resulting from the availability and depth of data. It does not attempt to answer every question about women’s entrepreneurship in MENA. Indeed, it may raise more questions than it answers. The hope is to spur greater interest in the topic among researchers and policy makers.
Issue: 44824
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Doing Business: Women in Africa - World Bank (World Bank, 2008)
Women in Africa
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

A Green Revolution in Southern Niassa? A field study from a small farmer perspective about possibilities and obstacles for a Green Revolution. - Karin Gatu; Sofia Rodman (Växjö University, 2007)
The aim of this field study was to analyze, by taking into consideration the small farmers’ perspective, the possibilities and obstacles for an implementation of a Green Revolution in southern Niassa, Northern Mozambique. The authors also ask: in what sense are the findings in Asia, presented by Djurfeldt, relevant for thesituation in southern Niassa?
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura

Adverse incorporation, social exclusion and chronic poverty - Hickey, Samuel; Andries du Toit (Institute for Development Policy and Management, School of Environment and Development, University of Manchester, 2007)
There are a number of compelling reasons to focus on the ways in which the processes and relations of adverse incorporation and social exclusion (AISE) underpin chronic poverty. In particular, AISE research draws attention to the causal processes that lead poverty to persist, and to the politics and political economy of these processes and associated relationships over time. Specific dimensions of AISE are explored in relation to chronic poverty – namely political, economic, socio-cultural and spatial – and are found to relate closely to long-term historical processes, particularly concerning the nature and forms of capitalism, different stages and types of state formation, and institutionalised patterns of social norms and attitudes. However, it is also stressed that much of the promise of AISE research lies in its capacity to cross analytical boundaries and capture the multi-dimensional and interlocking character of long-term deprivation. This analysis suggests a number of fruitful areas for research, most of which are currently under-explored in poverty research. In methodological terms, there are benefits to adopting integrated qualitative-quantitative approaches when investigating AISE, although it is argued that (a) the relational nature of AISE and the limitations of quantitative data may dictate that qualitative work should take priority here and (b) that more historical and theoretically oriented forms of research are particularly appropriate in studying AISE. To think about challenging AISE involves shifting the frame from policy to politics and from specific anti-poverty interventions to longer-term development strategies, particularly in terms of industrialisation and labour market restructuring, moves towards developmental states and supporting shifts from clientelism to citizenship. However, a range of more immediate development policy interventions may also be able to make headway in challenging the forms of AISE that perpetuate poverty.
OCLC: 317916213
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Niassa Agricultural Development Project (NADP): Completion Evaluation - International Fund for Agricultural Development (International Fund for Agricultural Development, 2007)
Evaluation report of IFAD's Niassa Agricultural Development Project (NADP).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; poverty / pobreza

Sex, Food and Female Power: Discussion of Data Material from Northern Mozambique - Arnfred, Signe (Sexualities, 2007)
Issues of sex and food are often inscribed in male/female relationships. Frequently in a western context sex is perceived as a site of male power and female subordination, while food and cooking are seen as female domains, but still sites of subordination, as elements of women's household chores. In this article, looking at issues of sex and food in a rural matrilineal setting, power aspects of male/female relationships as mediated through sex and food emerge somewhat differently. Sexual proficiency is here a woman's art, mastered by old women and transmitted to the young. Also, in a setting where daily life is largely based on subsistence production, food and cooking become domains of power, again with old women in control. Based on fieldwork in northern Mozambique and with reference to African feminist conceptualizations of male/female power relationships, the article makes a case for rurality and ‘tradition’ not necessarily being adverse to female power in social relationships.
Publisher: SAGE Publications Ltd
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; gender / género; youth / juventude

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Traditions and transitions : Islam and chiefship in Northern Mozambique, ca. 1850-1974 - Bonate, Liazzat J K (2007)
This thesis is based on the archival and fieldwork research, and sheds light on the area which has been little studied or reflected in scholarly literature: Islam in Northern Mozambique. Its particular focus is on African Muslim leadership in Northern Mozambique, which has historically incorporated Islamic authority and chiefship. The link between Islam and the chiefly clans existed since the eight century when Islam made inroads into the northern Mozambican coast and became associated with the Shirazi ruling elites. With the involvement of the region in the international slave trade during the nineteenth century, the Shirazi clans secured alliances with the most powerful mainland chiefs through conquest and kinship relations in order to access supplies of slaves from the mainland. This process was accompanied by a massive expansion of Islam from the coast into the hinterland. The alliances between the Shirazi at the coast and the chiefdoms further into the interior resulted in a network of paramount chiefs and their subordinates making up the bulk of Muslim slave-raiders, who established the limits between themselves (the Maca, Muslims and 'civilized') and those to be enslaved (the Makua and Lomwe, derogatory terms, meaning savagery, i.e., 'non-Muslims' and 'uncivilized')
Publisher: University of Cape Town
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Palgrave Macmillan, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça

Indonesia After the Asian Crisis* - Hill, Hal; Shiraishi, Takashi (Asian Economic Policy Review, 2007)
Indonesia was deeply affected by the 1997–1998 crisis, more so than its East Asian neighbors. Its economic contraction was deeper and more prolonged. It was the only one to experience a (temporary) loss of macroeconomic control. It also suffered “twin crises,” in the sense that its serious economic and financial problems were accompanied by regime collapse. Consequently, recovery was a slow and complex process, as new institutions had to be created, and old ones reformed under successive short-lived administrations. But this process is largely over. The directly elected president with a strong popular mandate is in power. The new institutional framework for economic policy-making is in place. Macroeconomic stability has been restored. Although growth has yet to return to pre-crisis levels, by 2004 per capita income and poverty incidence had recovered to levels prevailing in the mid-1990s, and in the circumstances economic recovery has arguably proceeded about as quickly as could reasonably have been expected.
Number: 1 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1748-3131.2007.00058.x
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; economic development / desenvolvimento económico

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

Business licensing and one stop shops in Indonesia - Steer, Liesbet (The Asia Foundation, 2006)
In 2001, Indonesia embarked on a decentralization process that has had a dramatic impact on the local political landscape, especially in relation to taxation and administrative processes. Rules and procedures that govern licensing, registration, some taxes and user charges have largely been devolved to local governments. A significant number of new licenses and charges have been created at the local level, and most licenses are issued through a complicated system of procedures and agencies. Licensing has become one of the most important barriers to business formalization and growth in Indonesia. The local licensing framework in Indonesia has three key problems, raising transactions costs and inefficiencies. Licensing reform through One Stop Shops (OSS). The Asia Foundation OSS technical assistance program. The methodology has proven to be highly effective.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

War and reconstruction in northern Mozambique - Brück, Tilman (The Economics of Peace and Security Journal, 2006)
The article discusses some of the economic effects of war in northern Mozambique. It indicates how the historical and structural features of the economy of northern Mozambique restricted post-war reconstruction and post-war poverty alleviation. These features include the dominance of only a few cash crops for export, the absence of much rural trading, poor communication infrastructure, and weak political and state institutions. The specific nature of the internal war further weakened the state through the collapse of tax revenue and export earnings and the massive growth of debt and aid, of which little reached rural northern Mozambique. The article also summarizes key aspects of the geography, climate, markets, and social institutions of northern Mozambique, which define the potential production opportunities for peasant households. Finally, the article suggests how post-war reconstruction could have been more effective in achieving faster post-war poverty alleviation in northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; conflict - civil war / conflito - guerra civil; health / saúde

National Governance and Local Chieftaincy : A Multi-level Power Assessment of Mozambique from Niassa's Perspective - Nilsson, Anders; Åkesson, Gunilla (Sida, 2006)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
ISSN 0805-505X ISBN 82-8062-172-5
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Moçambique Inquérito Demográfico e de Saúde 2003 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2005)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Number: 2
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Chains of fortune: linking women producers and workers with global markets - Commonwealth Secretariat; Carr, Marilyn (2004)
Globalisation opens up new economic opportunities if poor women producers and workers are enabled to take advantage of them. The need for assistance differs between independent producers on the one hand and wage workers in export industries on the other. In the former case, the need mainly is for increased access to global markets. In the latter case, the need mainly is for better organising so as to bargain for better wages and working conditions. This edited volume brings together six case studies. Three link local producers with global markets: a cocoa cooperative in Ghana; an organic coconut oil producer in Samoa; and small enterprises in Mozambique. Three focus on improving the working conditions of wage workers in global value chains: those in the fruit exporting industry in South Africa; those in the garment export industry in Bangladesh; and those in the newly created call centres in India. Each case study is written by a team of international and national researchers and aims to present decision makers with concrete examples which can spread the gains of globalisation to the working poor through shifting the balance of access, power and returns within global value chains.
OCLC: 929085505
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

Indústria e industrialização em Moçambique: análise da situação actual e linhas estratégicas de desenvolvimento - Castel-Branco, Carlos (Quaderni della Cooperazione Italiana, 2003)
Published as part of the working paper series of the Italian Cooperation. Discusses the dynamics of industrialization in the early stages of large FDI boom in Mozambique, as well as challenges ahead,
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água; higiene e saneamento; health / saúde; private sector / setor privado

Indonesia: Managing Decentralization - Ahmad, Ehtisham; Mansoor, Ali M. (International Monetary Fund, 2002)
The process of decentralization in Indonesia was initiated after a long period of autocratic rule. Despite the political imperatives, there is a need to carefully sequence the fiscal decentralization to ensure that financing follows the assignment of functions. The functions should be commensurate with the capacity to provide public services. The paper argues for the proper sequencing to avoid jeopardizing macroeconomic stability or the effective delivery of public services.
Google-Books-ID: EwjvYCqlFaoC
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

From ‘Abaixo’ to ‘chiefs of production’: Agrarian change in Nampula province, mozambique, 1975–87 - Dinerman, Alice (The Journal of Peasant Studies, 2001)
This article reconstructs key aspects of the evolving relationship between state institutions and former regulos (Portuguese‐appointed chiefs), in Nampula Province, Mozambique during the first 12 years of independence. In doing so, it simultaneously draws on and critiques two opposing interpretations of revolution and counterrevolution which have dominated scholarly production on post‐independence Mozambique and have polarized Mozambican studies in recent years. Against both sets of literature, my study finds that state socialism did not always and everywhere bring major disruptions to grassroots structures of authority; rather, many families who had been recognized by the Portuguese as royals were able, through a variety of strategies, to maintain their grip on local power. Secondly, I argue that the provincial government's enlistment of former regulos to serve as ‘chiefs of production’ was but one aspect of an attempt on the part of officialdom to recreate the most salient aspects of the colonial cotton regime rather than a war‐induced genuflection by the Frelimo regime to Renamo on the question of chiefly rule, as has been claimed by what I call ‘revisionist’ scholarship. Frelimo's refusal to acknowledge the role of villagization in agricultural decline throughout the country, a point raised and highlighted by revisionist writing is, however, crucial to understanding the ideological practices that helped justify and legitimate the return to Portuguese precedent on matters relating to rural labour. The reasons why Nampula was the site of these initiatives are explored.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150108438766
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; agriculture / agricultura; authority / autoridade

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Number: 71 Publisher: Southeast Asia Program Publications at Cornell University
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico